Thermosetting composition, method for manufacturing thermosetting sheet, thermally conductive sheet, heat dissipation laminate, heat dissipation circuit board, and power semiconductor device

By adjusting the composition and process of the thermosetting composition, the problems of reduced insulation performance and cracking at high temperatures were solved, achieving insulation performance retention and bonding stability under high temperature conditions. This makes it suitable for heat dissipation laminates, heat dissipation circuit boards, and power semiconductor devices.

CN123036346APending Publication Date: 2026-11-03MITSUBISHI CHEM CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202580021632.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-30
Filing Date
2025-03-19
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

During reflow soldering and under high-temperature conditions, the cured products of existing thermosetting compositions are prone to reduced insulation performance due to internal stress and external force, and are also prone to cracking or delamination during sintering, affecting the reliability and electrical transmission efficiency of power semiconductor devices.

Method used

Thermosetting compositions containing inorganic fillers and thermosetting compounds are used. By adjusting the composition and process conditions, the cured product is ensured to have excellent insulation properties and high-temperature resistance at high temperatures, avoiding cracking and bond peeling. Specific measures include adjusting the type and content of thermosetting compounds, crosslinking density, and low-temperature curing.

Benefits of technology

It achieves full retention of insulation performance after reflow soldering and avoids cracking and bond peeling under high temperature and external force conditions, ensuring electrical conductivity and continuous bond stability. It is suitable for heat dissipation laminates, heat dissipation circuit boards and power semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a thermosetting composition containing an inorganic filler and a thermosetting compound, as a thermosetting composition whose cured product is excellent in high-temperature resistance in which no cracks are generated in the cured product or no peeling occurs when the cured product is joined to a substrate under high-temperature conditions of 150°C or higher, such as a reflow soldering process, sintering bonding, or the like, and a thermosetting composition is proposed, which contains an inorganic filler and a thermosetting compound, characterized in that the value of the fracture energy of the cured product obtained by three-point bending measurement at 190°C of the thermosetting composition cured is 55 kPa or higher, and the value of the fracture energy obtained by three-point bending measurement at 150°C is 80 kPa or higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermosetting composition having thermosetting properties, such as a thermosetting composition whose cured form can be suitably used as a heat sink for a power semiconductor device, a method for manufacturing a thermosetting sheet using the thermosetting composition, a thermally conductive sheet using the thermosetting composition, and a heat dissipation laminate, a heat dissipation circuit board, and a power semiconductor device using the thermally conductive sheet. Background Technology

[0002] In devices that use semiconductors, the equipment that controls and converts power sources, etc., is called a "power semiconductor device".

[0003] Power semiconductor devices are typically configured such that power semiconductors and electronic components that perform power conversion and control are mounted on a base that functions as a heat sink.

[0004] In recent years, power semiconductor devices used in various fields such as railways, automobiles, industry, and ordinary household appliances are shifting from traditional Si power semiconductors to power semiconductors using SiC, AlN, GaN, etc., in order to further miniaturize, reduce costs, and increase efficiency.

[0005] Various technical challenges have been identified for the practical application of such power semiconductor devices, one of which is the issue of heat generation. While power semiconductor devices can achieve high output and high density by operating at high temperatures, there are concerns that the heat generated during switching and other processes may reduce the reliability of these devices.

[0006] Furthermore, in recent years, the increasing density of integrated circuits in the electrical / electronics field has led to significant heat generation, making heat dissipation an urgent technical issue. For example, in the stable operation of power semiconductor devices used to control central processing units in personal computers and motors in electric vehicles, heat dissipation components such as heat sinks and fins are indispensable for heat dissipation. As components that connect circuits including power semiconductors to heat dissipation components such as heat sinks, they must be able to balance thermal conductivity and insulation.

[0007] As components that can balance thermal conductivity and insulation, ceramic substrates with high thermal conductivity, such as alumina substrates and aluminum nitride substrates, have traditionally been used. However, ceramic substrates have technical problems such as being prone to cracking due to impact, being difficult to thin-film, and being difficult to miniaturize.

[0008] To address the technical problems in ceramic substrates as described above, extensive research has been conducted on heat sinks with good thermal conductivity and excellent insulation. In particular, attempts have been made to incorporate fillers into resins to obtain heat-dissipating resin sheets that meet high levels of thermal conductivity and insulation. Various oxides and nitrides have been used as fillers in such heat-dissipating resin sheets, and extensive research has been conducted (see, for example, Patent Document 1).

[0009] Hexagonal boron nitride was used as a filler in the heat dissipation resin sheet. Hexagonal boron nitride is typically a thin, plate-like crystal with high thermal conductivity in the planar direction but low thermal conductivity in the thickness direction. Furthermore, if plate-like boron nitride is incorporated into the heat dissipation resin sheet, it will be oriented parallel to the sheet surface during sheet formation, thus the thermal conductivity in the thickness direction of the sheet will never become good.

[0010] Boron nitride aggregates can be cited as a material for improving the thermal conductivity of a sheet in the thickness direction. It is well known that the thermal conductivity of a sheet in the thickness direction can be improved by using boron nitride aggregates. In particular, the applicant has previously developed boron nitride aggregates with a cardboard structure (see, for example, Patent Document 2).

[0011] Furthermore, the applicant has developed boron nitride aggregate particles with a relatively large average particle size and which rarely collapse even when pressure is applied (see, for example, Patent Document 3).

[0012] These boron nitride aggregates, by ensuring a heat conduction path based on the cardboard structure, achieve excellent thermal conductivity in the thickness direction of the heat dissipation resin sheet when incorporated into it. Furthermore, the boron nitride aggregates are formed without the use of additional adhesives. Therefore, even when external forces are applied during sheet formation, the cardboard structure is less likely to collapse, maintaining the heat conduction path and enabling heat dissipation in the thickness direction of the sheet, thus achieving excellent thermal conductivity (see, for example, Patent Documents 4 and 5).

[0013] In addition, as a molding method to improve the thermal conductivity in the thickness direction of the sheet, there is a known method that improves the thermal conductivity by making the boron nitride aggregate particles in the sheet come into surface contact with each other (see, for example, Patent Document 6).

[0014] The applicant has proposed a resin composition containing an inorganic filler and a thermosetting compound. In the solid component of the resin composition, the inorganic filler content is 50% by volume or more, and boron nitride filler (A) is 82% by volume or more among the inorganic fillers. The boron nitride filler includes an aggregated filler. The thermosetting compound contains an epoxy resin with a mass-average molecular weight of 5,000 or more. The epoxy equivalent (WPE) of the resin component in the resin composition is 100 ≤ WPE ≤ 300, and the storage modulus E' of the cured resin composition is 1 ≥ (E' at 270°C) / (E' at 30°C) ≥ 0.2 (Patent Document 7).

[0015] The applicant also proposes a thermosetting resin composition and a thermally conductive sheet formed from the thermosetting resin composition, the thermosetting resin composition containing a thermosetting compound, an inorganic filler and a polymer with a mass-average molecular weight of 10,000 or more, the thermosetting resin composition being characterized in that it contains boron nitride aggregate particles as the inorganic filler, and contains an epoxy compound and a benzoxazine compound as the thermosetting compound (Patent Document 8).

[0016] Existing technical documents

[0017] Patent documents

[0018] Patent Document 1: Japanese Patent Application Publication No. 2013-089670

[0019] Patent Document 2: Japanese Patent Application Publication No. 2015-006985

[0020] Patent Document 3: Japanese Patent Application Publication No. 2016-135730

[0021] Patent Document 4: International Publication No. 2015 / 119198

[0022] Patent Document 5: Japanese Patent Application Publication No. 2017-036415

[0023] Patent Document 6: International Publication No. 2019 / 189746

[0024] Patent Document 7: International Publication No. 2022 / 210686

[0025] Patent Document 8: International Publication No. 2023 / 182470 Summary of the Invention

[0026] The problem that the invention aims to solve

[0027] One of the processes in assembling power semiconductor devices is the reflow soldering process. In the reflow soldering process, the components are rapidly heated to melt the solder and bond the metal components together. A technical problem exists: during the high temperatures of the reflow soldering process, internal stress is applied due to component expansion and moisture, leading to degradation of components used in power semiconductor devices. For example, the insulation properties of the cured material decrease, resulting in reduced reliability of the power semiconductor device.

[0028] Therefore, cured products of thermosetting compositions containing inorganic fillers and thermosetting compounds are required to have sufficient insulation properties even after reflow soldering.

[0029] In addition, in recent years, in order to develop next-generation power semiconductor devices, and as a mounting technology with higher reliability, there is a greater demand for superior electrical transmission efficiency and continuous bonding stability under the condition of external force applied at high temperatures. Therefore, the use of silver sintering bonding has attracted attention.

[0030] Taking the example of bonding a semiconductor chip with a thermally conductive sheet to a support substrate by sintering, the semiconductor chip is first placed on a predetermined chip bonding location on the support substrate using a sintering bonding material under specified temperature and load conditions. Then, a high-temperature, high-pressure heating process is performed between the support substrate and the semiconductor chip thereon, causing the solvent in the sintering bonding material to evaporate and sintering to occur between the sinterable particles. As a result, a sintered layer is formed between the support substrate and the semiconductor chip, electrically connecting and mechanically bonding the semiconductor chip to the support substrate.

[0031] It is known that when a cured thermosetting composition containing inorganic fillers and thermosetting compounds is bonded to a substrate under high temperature conditions, such as by sintering, cracks or bond peeling may sometimes occur in the cured composition because external forces are applied in addition to internal stresses at high temperatures.

[0032] Therefore, the object of the present invention is to provide a thermosetting composition and a method for manufacturing a thermosetting sheet using the thermosetting composition, a thermally conductive sheet formed from a sheet-like cured product of the thermosetting composition, a heat-dissipating laminate having the thermally conductive sheet, a heat-dissipating circuit board, and a power semiconductor device, wherein the thermosetting composition containing inorganic fillers and thermosetting compounds not only has sufficient insulation properties after the curing process (also referred to as "cured product of thermosetting composition"), but also does not produce cracks or bond peeling in the cured product when the cured product is bonded to a substrate under conditions of further application of external force at high temperature, such as sintering bonding, and exhibits excellent high-temperature resistance.

[0033] Solution for solving the problem

[0034] In order to solve the above-mentioned technical problems, the present invention proposes the following solutions: a thermosetting composition, a thermally conductive sheet, a heat dissipation laminate, a heat dissipation circuit board, a power semiconductor device, and a method for manufacturing the thermosetting sheet.

[0035] [1] The first aspect of the present invention is a thermosetting composition containing an inorganic filler and a thermosetting compound, characterized in that the cured product formed by curing the thermosetting composition (also referred to as "cured product of thermosetting composition") has a fracture energy of 55 kPa or more as determined by three-point bending at 190°C, and a fracture energy of 80 kPa or more as determined by three-point bending at 150°C.

[0036] [2] The second aspect of the present invention is a thermosetting composition containing an inorganic filler and a thermosetting compound, characterized in that, when the fracture energy obtained by the curing of the thermosetting composition (also referred to as "cured thermosetting composition") by a three-point bending test at 190°C is set as x, and the fracture energy obtained by the three-point bending test at 150°C is set as y, the value of x / y is 0.7 or more and 1.15 or less, and the value of x is 55 kPa or more.

[0037] Furthermore, the second aspect of the present invention can also be conceived as both the first and second aspects.

[0038] [3] The third aspect of the present invention is a thermosetting composition, wherein in the first or second aspect, the cured thermosetting composition has a Young's modulus of 5.5 GPa or higher as determined by three-point bending at 190°C.

[0039] [4] The fourth aspect of the present invention is a thermosetting composition, wherein in any of the first to third aspects, the sheet-like cured product formed by curing the thermosetting composition (also referred to as "sheet-like cured product of thermosetting composition") has a thermal conductivity of 14 W / m·K or more in the thickness direction at 25°C.

[0040] [5] The fifth aspect of the present invention is a thermosetting composition, wherein in any of the first to fourth aspects, the insulation breakdown voltage of the thermosetting composition is 6.5 kV or higher when the thickness of the sheet-like cured product is 150 μm.

[0041] [6] The sixth aspect of the present invention is a thermosetting composition, wherein in any of the first to fifth aspects, the volume resistivity (1000V, 200℃) of the sheet-like cured product of the thermosetting composition is 3.0E+10Ωcm or more.

[0042] [7] The seventh aspect of the present invention is a thermosetting composition, wherein in any of the first to sixth aspects, the moisture absorption rate of the sheet-like cured product of the thermosetting composition is 0.7% by mass or more and 1.2% by mass or less.

[0043] [8] The eighth aspect of the present invention is a thermosetting composition, wherein in any of the first to seventh aspects, the thermosetting composition has a storage modulus of 6.0 GPa or more and 100 GPa or less at 200°C.

[0044] [9] The ninth aspect of the present invention is a thermosetting composition, wherein in any of the first to eighth aspects, the glass transition temperature (Tg) of the sheet-cured thermosetting composition is 170°C or higher.

[0045]

[10] The tenth aspect of the present invention is a thermosetting composition, wherein in any of the first to ninth aspects, it comprises an epoxy compound and at least one of a phenolic resin, a benzoxazine compound, a polyarylate, a cyanate ester and a maleimide.

[0046]

[11] The 11th aspect of the present invention is a thermosetting composition, in any of the 1st to 10th aspects, comprising an epoxy compound and a phenolic resin.

[0047]

[12] The 12th embodiment of the present invention is a thermosetting composition, wherein in any of the 1st to 11th embodiments, a multifunctional epoxy compound having 3 or more epoxy groups in a molecule and a mass-average molecular weight (Mw) of less than 5,000 is contained in the molecule.

[0048]

[13] The 13th embodiment of the present invention is a thermosetting composition comprising, in any of the 1st to 12th embodiments, a high molecular weight epoxy compound with a mass-average molecular weight (Mw) of 5,000 or more.

[0049]

[14] The 14th aspect of the present invention is a thermosetting composition in any of the 1st to 13th aspects, containing a polymer with a mass-average molecular weight (Mw) of 5,000 or more in a proportion of 5% by mass and less than 30% by mass relative to 100% by mass of the solid component after removing the inorganic filler.

[0050]

[15] The 15th aspect of the present invention is the thermosetting composition described in technical solution 1 or 2, wherein in any of the 1st to 13th aspects, a polymer with a mass-average molecular weight (Mw) of 5,000 or more is contained in a proportion of 5% by mass and 23% by mass or less of the solid component after removing the inorganic filler.

[0051]

[16] The 16th aspect of the present invention is a thermosetting composition in any of the 1st to 15th aspects, comprising an epoxy compound, wherein the epoxy equivalent (WPE) of the solid component after removing the inorganic filler from the solid component of the thermosetting composition is 200 g / equivalent or more and less than 250 g / equivalent.

[0052]

[17] The 17th embodiment of the present invention is a thermosetting composition in any of the 1st to 16th embodiments, containing boron nitride aggregated particles as the inorganic filler.

[0053]

[18] The 18th aspect of the present invention is a thermosetting composition in which the inorganic filler is contained in a proportion of 30% by mass or more and less than 90% by mass relative to 100% by mass of the solid content of the entire composition.

[0054]

[19] The 19th embodiment of the present invention is a thermally conductive sheet formed from a sheet-like cured product of a thermosetting composition of any one of the embodiments 1 to 18.

[0055]

[20] The 20th aspect of the present invention is a heat dissipation laminate having the thermally conductive sheet of the 19th aspect.

[0056]

[21] The 21st embodiment of the present invention is a heat dissipation circuit board having the thermally conductive sheet of the 19th embodiment.

[0057]

[22] The 22nd aspect of the present invention is a power semiconductor device having the thermally conductive sheet of the 19th aspect.

[0058]

[23] The 23rd aspect of the present invention is a method for manufacturing a thermosetting sheet, characterized in that the thermosetting composition of any of the 1st to 18th aspects is made into a film and subjected to low-temperature curing at an ambient temperature below 0°C.

[0059] Invention Effects

[0060] The thermosetting composition proposed in this invention not only has sufficient insulation properties after the reflow soldering process of its cured product, but also prevents cracks or delamination from occurring in the cured product when it is bonded to a substrate under conditions of further external force applied at high temperatures above 150°C, such as sintering.

[0061] The cured thermosetting composition proposed in this invention exhibits excellent high-temperature resistance, making it suitable for various processing applications in high-temperature regions above 150°C. For example, when bonded to a substrate by sintering, it ensures excellent electrical conductivity and sustained bonding stability. Therefore, it provides a thermally conductive sheet suitable for use in heat-dissipating laminates, heat-dissipating circuit boards, and power semiconductor devices. Attached Figure Description

[0062] Figure 1 This is a conceptual diagram of a particle cross-section of an example of boron nitride aggregates with a cardioid structure. Detailed Implementation

[0063] Hereinafter, an example of an embodiment of the present invention will be described in detail. However, the present invention is not limited to the following embodiment, and various changes can be made within its scope.

[0064] <<The Composition of the Invention>>

[0065] An example composition of an embodiment of the present invention (also referred to as "the composition of the present invention") is a thermosetting composition containing a thermosetting compound and an inorganic filler.

[0066] In this invention, "thermosetting composition" refers to a composition containing a compound or resin that has the property of curing by heat. That is, any curable composition that retains the potential for curing by heat is acceptable. It can be a composition that has been cured (also called "temporarily cured") to a state that retains the potential for curing, or it can be a composition that has not undergone any curing (also called "uncured").

[0067] Furthermore, in this invention, "resin" regardless of molecular weight includes organic compounds, monomers, oligomers, and polymers.

[0068] Furthermore, the composition of the present invention can be any of the molded articles formed into powder, slurry, liquid, solid or sheet forms. Therefore, for example, the composition of the present invention also includes a slurry-like thermosetting composition for use in the coating process described later, a sheet after the coating process, and a sheet after coating and drying processes, etc.

[0069] The thermosetting composition of the present invention, i.e. the cured product formed by curing the composition of the present invention (also referred to as "cured product of thermosetting composition"), is also referred to as "this cured product", and the sheet-like cured product formed by curing the sheet-like composition of the present invention (also referred to as "sheet-like cured product of thermosetting composition") is also referred to as "this sheet-like cured product".

[0070] Therefore, the compositions of the present invention can be cured by heating.

[0071] Furthermore, by molding the composition of the present invention into a sheet, a sheet-shaped thermosetting composition (also referred to as "this thermosetting sheet") can be produced, and by curing this thermosetting sheet, a sheet with thermal conductivity (also referred to as "this thermally conductive sheet") can be produced. That is, this thermally conductive sheet is both a cured sheet and a cured thermosetting sheet.

[0072] (Option 1)

[0073] In the first embodiment of the composition of the present invention, when the composition of the present invention is cured to form the cured product, the value of the fracture energy obtained by the three-point bending test at 190°C is 55 kPa or more, and the value of the fracture energy obtained by the three-point bending test at 150°C is 80 kPa or more.

[0074] The three-point bending test is a stress-applied test in which the sample is bent at three points: one from the center and two from below. Therefore, it is believed to be related to the resistance to bonding under conditions of internal stress and external force applied at high temperatures, such as reflow soldering and sintering.

[0075] That is, thermosetting compositions tend to accumulate strain during curing, and stress caused by strain tends to accumulate at temperatures before and after the curing temperature. For example, in the case of thermosetting compositions containing epoxy compounds, stress caused by strain at 120–200°C tends to accumulate. Therefore, by measuring the fracture strength at 150°C and 190°C in a three-point bending test, and by making them within a specified range, for example, resistance to reflow soldering under conditions of internal stress applied above 200°C and sintering under further external force can be obtained. It is believed that this not only has insulation resistance, but also is not prone to cracking in the sheet or peeling at the interface with the substrate.

[0076] If the fracture energy obtained by the three-point bending test at 190°C is 55 kPa or more, and the fracture energy obtained by the three-point bending test at 150°C is 80 kPa or more, then not only is it less likely to crack when stress caused by warping, strain, etc. is applied to the sheet-like cured material, but even after being subjected to internal stress at high temperature, such as in a reflow soldering process, the cured material will deteriorate less and can maintain its insulation withstand voltage. In addition, when it is bonded to the substrate by sintering under the condition of further external force applied at high temperature, it can prevent cracks from forming in the cured material or the bond from peeling off.

[0077] From the above perspective, the composition of the present invention preferably has a fracture energy of 55 kPa or more, more preferably 60 kPa or more, more preferably 70 kPa or more, and more preferably 80 kPa or more, obtained by three-point bending test at 190°C. The upper limit is not particularly limited, but is speculated to be around 500 kPa, and can be below 300 kPa or below 150 kPa.

[0078] Furthermore, the composition of the present invention preferably has a fracture energy of 80 kPa or more, more preferably 85 kPa or more, more preferably 90 kPa or more, and more preferably 100 kPa or more, obtained by three-point bending test at 150°C. The upper limit is not particularly limited, but is presumably around 500 kPa, and can be below 300 kPa or below 200 kPa.

[0079] (Option 2)

[0080] In a second embodiment of the composition of the present invention, when the composition of the present invention is cured, i.e. when the cured product is prepared, the fracture energy obtained by the three-point bending test at 190°C is set as x, and the fracture energy obtained by the three-point bending test at 150°C is set as y, the value of x / y is 0.7 or more and 1.15 or less, and the value of x is 55 kPa or more.

[0081] If the ratio (x / y) of the fracture energy x obtained by the three-point bending test at 190°C to the fracture energy y obtained by the three-point bending test at 150°C is 0.7 or more, and the value of x is 55 kPa or more, then the bending stress can be maintained even in the high-temperature region above 150°C. Therefore, even after being subjected to internal stress at high temperatures, such as in a reflow soldering process, the degradation of the cured material is minimal, and the insulation withstand voltage can be maintained. In addition, when further external force is applied at high temperatures and the material is bonded to a substrate by sintering, cracks or bond peeling can be prevented in the cured material. On the other hand, if the ratio (x / y) is 1.15 or less, the fracture energy at 150°C and 190°C is the same, and therefore the degradation during repeated heating cycles is less.

[0082] At this point, it is believed that the difference in fracture strength between 150℃ and 190℃ becomes smaller, and the ratio (x / y) is close to 1. Therefore, even if internal stress or external force is applied under conditions above 200℃, or if the temperature is subsequently reduced, the stress will be dispersed. In reflow soldering tests and sintering resistance tests, it not only has insulation resistance, but is also not prone to cracking in the sheet or peeling at the interface with the substrate.

[0083] From the above perspective, the ratio (x / y) of the fracture energy x obtained by three-point bending measurement at 190°C to the fracture energy y obtained by three-point bending measurement at 150°C is preferably 0.7 or more, more preferably 0.72 or more, more preferably 0.74 or more, and more preferably 0.76 or more. On the other hand, it is preferably 1.15 or less, more preferably 1.1 or less, more preferably 1.05 or less, and more preferably 1.03 or less.

[0084] Furthermore, the fracture energy x obtained by three-point bending measurement at 190°C of the cured composition of the present invention is preferably 55 kPa or more, more preferably 60 kPa or more, more preferably 70 kPa or more, and more preferably 80 kPa or more. The upper limit is not particularly limited, but is presumed to be around 500 kPa, and can be 300 kPa or less, or 150 kPa or less.

[0085] To prepare the composition of the present invention with the fracture energy obtained by three-point bending at 190°C, the fracture energy obtained by three-point bending at 150°C, or the ratio (x / y) of the fracture energy x obtained by three-point bending at 190°C to the fracture energy y obtained by three-point bending at 150°C within the aforementioned range, it is preferable to increase the crosslinking density of the cured product by adjusting the type and content of the thermosetting compound or curing agent, and to adjust the polymer concentration or low-temperature curing conditions, etc., so that the bending stress can be maintained even in the temperature region above the glass transition temperature (Tg) of the cured product. As a preferred example, the composition of the present invention is preferably prepared as follows: increasing the content of the multifunctional epoxy compound as a thermosetting compound and decreasing the content of the polymer, such as an epoxy polymer, thereby increasing the crosslinking points; then using a phenolic resin-based curing agent as a curing agent to promote crosslinking, thereby increasing the crosslinking density of the cured product, and performing low-temperature curing. By increasing the crosslinking density of the cured product, the contact force between the inorganic fillers is increased, resulting in an increase in the fracture energy at high temperatures. In addition, by increasing the force that maintains the contact between inorganic fillers, the thermal resistance between inorganic fillers can be reduced, for example, the thermal conductivity can be improved.

[0086] However, it is not limited to the methods described above.

[0087] Furthermore, the methods for determining the fracture energy of this cured material by three-point bending at 190°C and by three-point bending at 150°C can refer to the methods in the embodiments described later.

[0088] The composition of the present invention is further preferably such that, when the composition of the present invention is cured, i.e., when the cured product is prepared, the fracture energy of the cured product at 190°C is within the above-mentioned range, and the fracture energy of the cured product at 150°C is within the above-mentioned range, and the ratio (x / y) of the fracture energy x at 190°C to the fracture energy y at 150°C is within the above-mentioned range.

[0089] (Three-point bending test at 190℃: Young's modulus)

[0090] Preferably, when the composition of the present invention is cured to form the cured product, the Young's modulus of the cured product, as determined by a three-point bending test at 190°C, is 5.5 GPa or higher.

[0091] If the Young's modulus of this cured material is 5.5 GPa or higher as determined by three-point bending at 190°C, it is not easy to crack when stress caused by warping, strain, etc. is applied to this sheet-like cured material. Even after being subjected to internal stress at high temperature, such as in a reflow soldering process, the cured material deteriorates less and can maintain its insulation withstand voltage. Furthermore, when further external force is applied at a high temperature of 150°C or higher and it is bonded to a substrate by sintering, cracks or bond peeling can be prevented in this cured material.

[0092] From the above perspective, the Young's modulus of the composition of the present invention, as determined by three-point bending at 190°C, is preferably 5.5 GPa or higher, more preferably 5.6 GPa or higher, more preferably 5.7 GPa or higher, more preferably 5.8 GPa or higher, more preferably 5.9 GPa or higher, and more preferably 6.0 GPa or higher. The upper limit is not particularly limited, but is presumably around 100 GPa, and can be below 50 GPa or below 10 GPa.

[0093] (Three-point bending test at 150℃: Young's modulus)

[0094] Preferably, when the composition of the present invention is cured to form the cured product, the Young's modulus of the cured product obtained by three-point bending test at 150°C is 5.5 GPa or higher.

[0095] If the Young's modulus of this cured material is 5.5 GPa or higher as determined by three-point bending at 150°C, it is not easy to crack when stress caused by warping, strain, etc. is applied to this sheet-like cured material. Even after being subjected to internal stress at high temperature, such as in a reflow soldering process, the cured material deteriorates less and can maintain its insulation withstand voltage. Furthermore, when further external force is applied at a high temperature of 150°C or higher and it is bonded to a substrate by sintering, cracks or bond peeling can be prevented in this cured material.

[0096] From the above perspective, the Young's modulus of the composition of the present invention, as determined by three-point bending at 150°C, is preferably 5.5 GPa or higher, more preferably 5.8 GPa or higher, more preferably 6.0 GPa or higher, and even more preferably 6.3 GPa or higher. The upper limit is not particularly limited, but is presumably around 100 GPa, and can be below 50 GPa or below 10 GPa.

[0097] To prepare the composition of the present invention with Young's modulus values ​​obtained by three-point bending at 190°C and Young's modulus values ​​obtained by three-point bending at 150°C within the aforementioned range, it is preferable to increase the crosslinking density of the cured product by adjusting the type and content of the thermosetting compound or curing agent, and to adjust the polymer concentration or low-temperature curing conditions, thereby preparing the composition of the present invention so that the cured product can maintain flexural stress in the temperature region above the glass transition temperature (Tg). As a preferred example, the composition of the present invention is preferably prepared as follows: increasing the content of the multifunctional epoxy compound as a thermosetting compound and decreasing the content of the polymer, such as an epoxy polymer, thereby increasing the crosslinking points; then using a phenolic resin-based curing agent as a curing agent to promote crosslinking, thereby increasing the crosslinking density of the cured product; and then performing low-temperature curing. By increasing the crosslinking density of the cured product, the Young's modulus at high temperatures can be increased.

[0098] However, it is not limited to the methods described above.

[0099] Furthermore, the method for determining the Young's modulus value obtained by the three-point bending test at 150°C and 190°C of this cured material can refer to the method in the embodiments described later.

[0100] (thermal conductivity)

[0101] Preferably, when the composition of the present invention is formed into a sheet and cured, i.e., when the sheet-shaped cured product is prepared, the thermal conductivity of the sheet-shaped cured product in the thickness direction at 25°C is 14 W / m·K or higher.

[0102] If the thermal conductivity in the thickness direction of this sheet-like cured material is 14 W / m·K or higher at 25°C, it can also be used in power semiconductor devices that enable power semiconductors to operate at high temperatures.

[0103] From the above perspective, the composition of the present invention preferably has a thermal conductivity of 14 W / m·K or more in the thickness direction of the sheet-like cured material at 25°C, more preferably 15 W / m·K or more, and even more preferably 17 W / m·K or more.

[0104] In order to prepare the composition of the present invention with the thermal conductivity of the sheet-like cured product within the above-mentioned range, the type of thermosetting compound, the type and content of inorganic filler, the conditions in the low-temperature curing process, the conditions in the pressurizing process, and the conditions in the curing process can be adjusted, for example. However, it is not limited to these methods.

[0105] Furthermore, the method for measuring the thermal conductivity in the thickness direction of this sheet-like cured material can be referred to the method in the embodiments described later.

[0106] (Insulation breakdown voltage (BDV))

[0107] Preferably, when the composition of the present invention is formed into a sheet and cured, i.e., when the sheet-shaped cured product is prepared, the insulation breakdown voltage of the sheet-shaped cured product is 6.5kV or higher when the thickness of the sheet-shaped cured product is 150μm.

[0108] If the insulation breakdown voltage of this sheet-like cured material is above 6.5kV, it can also be used in power semiconductor devices that enable power semiconductors to operate at high voltages.

[0109] From the above perspective, the insulation breakdown voltage of the sheet-like cured composition of the present invention is preferably 6.5kV or higher, more preferably 7kV or higher, more preferably 7.5kV or higher, more preferably 8kV or higher, and more preferably 9kV or higher.

[0110] In order to prepare the composition of the present invention such that the insulation breakdown voltage of the sheet-like cured material falls within the aforementioned range, the type of thermosetting compound, the type and content of the inorganic filler, the conditions in the low-temperature curing process, the conditions in the pressurization process, and the conditions in the curing process can be adjusted, for example. However, it is not limited to these methods.

[0111] Furthermore, the method for determining the insulation breakdown voltage of this sheet-like cured material can be referred to the method in the embodiments described later.

[0112] (Volume resistivity)

[0113] Preferably, when the composition of the present invention is formed into a sheet and cured, i.e., when the sheet-shaped cured product is prepared, the volume resistivity (1000V, 200℃) of the sheet-shaped cured product is 3.0E+10Ωcm or more.

[0114] If the volume resistivity of this sheet-like cured material is 3.0E+10Ωcm or higher, it is good from the point of view of electrical insulation and is therefore preferred.

[0115] From the above perspective, the volume resistivity of the cured sheet of the composition of the present invention is preferably 3.0E+10Ωcm or more, more preferably 3.1E+10Ωcm or more, and even more preferably 3.2E+10Ωcm or more.

[0116] To prepare the composition of the present invention with a volume resistivity within the aforementioned range for the cured sheet, methods such as adjusting the type and content of the thermosetting compound or curing agent to increase the crosslinking density of the cured product, and adjusting the polymer concentration so that the cured product can maintain electrical insulation even in temperature regions above the glass transition temperature (Tg). As a preferred example, the composition of the present invention is preferably prepared by increasing the proportion of the multifunctional epoxy compound as the thermosetting compound and decreasing the proportion of the polymer, such as the epoxy polymer, to increase the crosslinking points; using a phenolic resin-based curing agent to promote crosslinking and increase the crosslinking density of the cured product; and then performing low-temperature curing. However, the method is not limited to these methods.

[0117] Furthermore, the method for measuring the volume resistivity (1000V, 200℃) of this sheet-like cured material can be referred to the method in the embodiments described later.

[0118] (Moisture absorption rate)

[0119] Preferably, when the composition of the present invention is formed into a sheet and cured, i.e., when the sheet-shaped cured product is prepared, the moisture absorption rate of the sheet-shaped cured product is 0.7% by mass or more and 1.2% by mass or less.

[0120] If the moisture absorption rate of the sheet-like cured material is 0.7% by mass or more, the absorbed moisture forms hydrogen bonds with the hydroxyl groups in the sheet-like cured material, thereby strengthening the sheet-like cured material and improving its bending resistance, which is preferred. On the other hand, if it is 1.2% by mass or less, it is good from the viewpoint of moisture absorption and reflow soldering resistance, and is therefore preferred.

[0121] From the above perspective, the moisture absorption rate of the cured sheet-like composition of the present invention is preferably 0.7% by mass or more, more preferably 0.72% by mass or more, and even more preferably 0.75% by mass or more. On the other hand, it is preferably 1.2% by mass or less, more preferably 1.1% by mass or less, and even more preferably 1.0% by mass or less.

[0122] To prepare the composition of the present invention with a moisture absorption rate within the aforementioned range for the cured sheet, examples include: methods to enhance crosslinking by adjusting the amount of epoxy compounds other than epoxy monomers (i.e., epoxy polymers) and the amount of curing agent, or methods to adjust the hydroxyl concentration in the resin components, and methods to adjust low-temperature curing conditions. As a preferred example, the composition of the present invention is preferably prepared by increasing the proportion of the multifunctional epoxy compound as a thermosetting compound and decreasing the proportion of the polymer, such as the epoxy polymer, thereby increasing the number of crosslinking points; using a phenolic resin-based curing agent as the curing agent to promote crosslinking and increase the crosslinking density of the cured product; and then performing low-temperature curing. However, the method is not limited to these methods.

[0123] Furthermore, the method for determining the moisture absorption rate of this sheet-like cured material can be referred to the method in the embodiments described later.

[0124] (Energy storage modulus (E'))

[0125] Preferably, when the composition of the present invention is formed into a sheet and cured, i.e., when the sheet-shaped cured product is prepared, the storage modulus of the sheet-shaped cured product at 200°C is 6.0 GPa or more and 100 GPa or less.

[0126] By ensuring that the storage modulus of this sheet-like cured material is within the specified range at 200°C, it is possible to achieve the effect that cracks are less likely to form in this sheet-like cured material at high temperatures.

[0127] From the above perspective, the storage modulus of the sheet-like cured product of the composition of the present invention at 200°C is preferably 6.0 GPa or more, more preferably 7.0 GPa or more, more preferably 7.5 GPa or more, and more preferably 7.7 GPa or more. On the other hand, it is preferably 100 GPa or less, more preferably 90 GPa or less, more preferably 80 GPa or less, and can be 50 GPa or less, 20 GPa or less, or 15 GPa or less.

[0128] To prepare the composition of the present invention with the storage modulus of the sheet-like cured product within the aforementioned range at 200°C, one can adjust the epoxy equivalent of the resin component, the amount of multifunctional epoxy resin, the ratio of epoxy polymer to epoxy compound other than epoxy polymer, or the low-temperature curing conditions. As a preferred example, the composition of the present invention is preferably prepared by increasing the proportion of the multifunctional epoxy compound as a thermosetting compound and decreasing the proportion of the polymer, such as the epoxy polymer, thereby increasing the crosslinking points. Furthermore, a phenolic resin-based curing agent is used as the curing agent to promote crosslinking, thereby increasing the crosslinking density of the cured product, and then low-temperature curing is performed. However, this method is not limited to these methods.

[0129] Furthermore, the storage modulus of the sheet-like cured material at 200°C can be determined as follows: A sheet-like thermosetting composition is laminated, the sample thickness is adjusted to 0.1–1.0 mm, and it is heated and cured to form a sheet-like cured material. This sheet-like cured material is then cut into short strips with a width of 4 mm, and the result is determined by a dynamic viscoelasticity test under tensile mode. More specifically, the method for determining the storage modulus of the sheet-like cured material at 200°C can be found in the methods described in the examples below.

[0130] (Glass transition temperature (Tg))

[0131] Preferably, when the composition of the present invention is formed into a sheet and cured, i.e., when the sheet-shaped cured product is prepared, the glass transition temperature (Tg) of the sheet-shaped cured product is 170°C or higher.

[0132] If the glass transition temperature (Tg) of this sheet-like cured material is 170°C or higher, then the sheet-like cured material is strong and tough even in the high-temperature region above 175°C, and is therefore preferred. Regarding the upper limit, from the viewpoint of the ease of cracking of this sheet-like cured material, it is preferably 300°C or lower.

[0133] From the above perspective, the glass transition temperature (Tg) of the cured sheet of the composition of the present invention is preferably 170°C or higher, more preferably 175°C or higher, and even more preferably 180°C or higher. On the other hand, it is preferably 300°C or lower, more preferably 275°C or lower, and even more preferably 250°C or lower.

[0134] To prepare the composition of the present invention with the glass transition temperature (Tg) of the cured sheet within the aforementioned range, methods such as adjusting the type and content of the thermosetting compound or curing agent to increase the crosslinking density of the cured product and adjusting the polymer concentration can be employed. As a preferred example, the composition of the present invention is preferably prepared by increasing the proportion of the multifunctional epoxy compound as the thermosetting compound and decreasing the proportion of the polymer, such as an epoxy polymer, thereby increasing the number of crosslinking points; then using a phenolic resin-based curing agent as the curing agent to promote crosslinking, thereby increasing the crosslinking density of the cured product; and finally, performing low-temperature curing. However, the method is not limited to these methods.

[0135] For the method of determining the glass transition temperature (Tg) of this sheet-like cured material, please refer to the method in the examples described later.

[0136] (WPE with resin composition)

[0137] When the composition of the present invention contains an epoxy compound, the component after removing the solvent and inorganic filler from the composition of the present invention (also referred to as the "resin component"), in other words, the epoxy equivalent (WPE) of the solid component after removing the inorganic filler from the solid component of the composition of the present invention is preferably WPE < 250 g / equivalent.

[0138] The solid components of the composition of the present invention refer to the components after removing the solvent from the composition of the present invention.

[0139] Here, epoxy equivalent (WPE) refers to the mass (g / equivalent) of the resin component per 1 equivalent of epoxy groups.

[0140] If the epoxy equivalent (WPE) of the resin component in the composition of the present invention is adjusted to the above-mentioned range, the flexibility of the composition of the present invention can be adjusted, and the crosslinking density in the cured product can be adjusted to improve the flexural strength. Furthermore, the retaining force of the inorganic filler can be adjusted, and the thermal conductivity of the sheet-like cured product can be improved.

[0141] From the above perspective, the epoxy equivalent (WPE) of the resin component in the composition of the present invention is preferably less than 250 g / equivalent, more preferably less than 245 g / equivalent, more preferably less than 240 g / equivalent, more preferably less than 235 g / equivalent, and more preferably less than 230 g / equivalent.

[0142] On the other hand, from the viewpoint of ensuring the film-forming properties of the uncured thermosetting sheet and the toughness of the cured sheet, the epoxy equivalent (WPE) of the resin component in the composition of the present invention is preferably 100 g / equivalent or more, more preferably 110 g / equivalent or more, more preferably 120 g / equivalent or more, more preferably 150 g / equivalent or more, more preferably 170 g / equivalent or more, more preferably 200 g / equivalent or more, and particularly more preferably 210 g / equivalent or more.

[0143] To adjust the epoxy equivalent (WPE) of the resin component of the composition of the present invention to the above-mentioned range, the following methods can be employed: adjusting the content ratio of epoxy compounds, such as epoxy polymers and multifunctional epoxy compounds, having a specified epoxy equivalent, or adjusting the type and content of the curing agent. As a preferred example, it is preferable to increase the content ratio of the multifunctional epoxy compound, which is a thermosetting compound, and decrease the content ratio of the polymer, such as the epoxy polymer, and then use a phenolic resin-based curing agent as the curing agent and adjust its content to adjust the epoxy equivalent (WPE) of the resin component of the composition of the present invention to the above-mentioned range. However, these methods are not the only options.

[0144] <Thermosetting compounds>

[0145] Examples of thermosetting compounds contained in the compositions of the present invention include: epoxy compounds, phenolic resins, unsaturated polyester resins, melamine resins, urea-formaldehyde resins, benzoxazine compounds, cyanate esters, and maleimides.

[0146] The content of thermosetting compound is preferably 10% by mass or more and 70% by mass or less, relative to 100% by mass of the component (also called "solid component") after removing volatile components such as solvents in the composition of the present invention.

[0147] If the content of thermosetting compound is 10% by mass or more, the formability is good, and therefore it is preferred. On the other hand, if it is 70% by mass or less, the content of other components can be ensured, for example, the thermal conductivity can be improved, and therefore it is preferred.

[0148] From the above perspective, relative to 100% by mass of the solid components in the composition of the present invention, the content of the thermosetting compound is preferably 10% by mass or more and 70% by mass or less, more preferably 15% by mass or more, more preferably 20% by mass or more, more preferably 25% by mass or more, and more preferably contains 60% by mass or less.

[0149] Furthermore, when using an epoxy compound as a thermosetting compound, it is preferable to use a curing agent and a thermosetting catalyst described later. In this case, the curing agent and thermosetting catalyst are equivalent to thermosetting compounds and are therefore included in the thermosetting compounds mentioned above in "content of thermosetting compounds".

[0150] (Epoxy compounds)

[0151] The compositions of the present invention preferably contain an epoxy compound as a thermosetting compound.

[0152] In the thermosetting compound contained in the composition of the present invention, the epoxy compound preferably accounts for 30 to 100% by mass, more preferably 40% by mass or more, more preferably 50% by mass or more, more preferably 60% by mass or more, and more preferably 70% by mass or more.

[0153] In addition, the epoxy compound at this time also includes the epoxy polymer described later.

[0154] The epoxy compound included in the composition of the present invention as a thermosetting compound can be any compound having one or more ethylene oxide rings, i.e., epoxy groups, within one molecule.

[0155] The epoxy group contained in the epoxy compound can be either an alicyclic epoxy group or a glycidyl group. From the viewpoint of reaction rate or heat resistance, a glycidyl group is more preferred.

[0156] Examples of epoxy compounds include: silicon compounds containing epoxy groups, aliphatic epoxy compounds, bisphenol A or F type epoxy compounds, phenolic varnish type epoxy compounds, aromatic epoxy compounds, alicyclic epoxy compounds, glycidyl ester type epoxy compounds, multifunctional epoxy compounds, and high molecular weight epoxy compounds.

[0157] The epoxy compound may be a compound containing aromatic epoxy groups. Specific examples include: bisphenol-type epoxy compounds obtained by glycidylating bisphenols such as bisphenol A, bisphenol F, bisphenol AD, bisphenol S, tetramethylbisphenol A, tetramethylbisphenol F, tetramethylbisphenol AD, tetramethylbisphenol S, and tetrafluorobisphenol A; biphenyl-type epoxy compounds; epoxy compounds obtained by glycidylating dihydroxynaphthalene, 9,9-bis(4-hydroxyphenyl)fluorene, and other diphenols; and epoxy compounds obtained by glycidylating 1,1,1-tris(4-hydroxyphenyl)... Epoxides obtained by glycidylating triphenols such as methane; epoxy compounds obtained by glycidylating tetraphenols such as 1,1,2,2-tetra(4-hydroxyphenyl)ethane; phenolic varnish-type epoxy compounds obtained by glycidylating phenolic varnishes such as phenolic varnish, cresol varnish, bisphenol A varnish, and brominated bisphenol A varnish; epoxy compounds having a dicyclopentadiene skeleton; and epoxy compounds having a naphthalene skeleton. Preferably, the epoxy compounds include those having at least one skeleton selected from epoxy compounds having a biphenyl skeleton, epoxy compounds having a dicyclopentadiene skeleton, and epoxy compounds having a naphthalene skeleton.

[0158] (Multifunctional epoxy compounds)

[0159] The compositions of the present invention preferably comprise the polyfunctional epoxy compounds described below.

[0160] A multifunctional epoxy compound is an epoxy compound having two or more epoxy groups in one molecule and a mass-average molecular weight (Mw) of less than 5,000. Preferably, the composition of the present invention comprises a multifunctional epoxy compound having three or more epoxy groups in one molecule and a mass-average molecular weight (Mw) of less than 5,000. More preferably, the multifunctional epoxy compound comprises a compound having four or more epoxy groups in one molecule.

[0161] By containing such a multifunctional epoxy compound, highly polar epoxy groups can be introduced at a high density, thereby increasing the effectiveness of physical interactions such as van der Waals forces and hydrogen bonds. For example, this improves the adhesion between the thermally conductive sheet formed from the composition of the present invention and conductive materials such as metal plates and circuit boards. Furthermore, by containing a multifunctional epoxy compound, the storage modulus of the thermally conductive sheet can be increased. This allows the cured material to exhibit a strong anchoring effect when it penetrates the uneven surface of the conductive material, further improving the adhesion between the thermally conductive sheet and conductive materials such as metal plates and circuit boards. Moreover, by containing a multifunctional epoxy compound, particularly a multifunctional epoxy compound having three or more epoxy groups per molecule, the crosslinking density of the cured material can be further increased, thereby improving the fracture energy obtained by three-point bending tests at 150°C and 190°C.

[0162] On the other hand, by including polyfunctional epoxy compounds, the hygroscopicity of the compositions of the present invention tends to increase, but by increasing the reactivity of the epoxy groups, the amount of hydroxyl groups during the reaction can be reduced, thus suppressing the increase in hygroscopicity.

[0163] Furthermore, by combining the epoxy polymer described later with a multifunctional epoxy compound to prepare the composition of the present invention, it is possible to achieve both high elasticity and low moisture absorption of the thermally conductive sheet.

[0164] From the viewpoint of improving the storage modulus of the cured material, especially at high temperatures where heat generation is high in power semiconductor devices and other applications, any epoxy compound having two or more epoxy groups per molecule is acceptable. Preferably, an epoxy compound having three or more epoxy groups per molecule is preferred, and even more preferably, an epoxy compound having four or more epoxy groups per molecule is preferred. By having multiple epoxy groups, particularly glycidyl groups, per molecule, the crosslinking density of the cured material is increased, resulting in higher strength of the thermally conductive sheet. Consequently, when internal stress is generated in the thermally conductive sheet at high temperatures, such as during reflow soldering or sintering, the thermally conductive sheet will not deform or break and will maintain its shape, thereby suppressing the formation of pores or other voids within the thermally conductive sheet.

[0165] Furthermore, from the viewpoint of adjusting the crosslinking properties of this thermally conductive sheet, the molecular weight of the polyfunctional epoxy compound, particularly a polyfunctional epoxy compound having three or more epoxy groups per molecule, is preferably 800 or less, more preferably 700 or less, more preferably 650 or less, particularly 100 or more or 630 or less, and more preferably 200 or more or 600 or less. Additionally, to ensure good operability of the composition of the present invention and the thermosetting sheet, it is preferable to include a polyfunctional epoxy compound that is liquid at 25°C.

[0166] Furthermore, from the viewpoint of achieving lower moisture absorption and higher cross-linking, multifunctional epoxy compounds preferably do not contain amine or amide structures containing nitrogen atoms.

[0167] From the viewpoint of improving the heat resistance of this thermally conductive sheet, the epoxy equivalent of the polyfunctional epoxy compound, especially the polyfunctional epoxy compound having three or more epoxy groups per molecule, is preferably 75 g / equivalent or more, more preferably 80 g / equivalent or more. On the other hand, from the viewpoint of improving solubility in solvents, it is preferably 200 g / equivalent or less, more preferably 180 g / equivalent or less, more preferably 160 g / equivalent or less, and more preferably 150 g / equivalent or less.

[0168] As a multifunctional epoxy compound, any epoxy compound having two or more epoxy groups in one molecule is acceptable. For example, it is preferable to have three or more epoxy groups in one molecule and a molecular weight of 800 or less, of which 650 or less is preferred. For example, EX321L, DLC301, DLC402, etc., manufactured by Nagase ChemteX can be used.

[0169] These multifunctional epoxy compounds can be used in combination with one or more.

[0170] (Epoxy polymer)

[0171] From the viewpoint of ensuring film-forming properties, the composition of the present invention preferably contains a high molecular weight epoxy compound (also known as "epoxy polymer") with a mass-average molecular weight (Mw) of 5,000 or more.

[0172] Examples of epoxy polymers include phenoxy resins having at least one backbone selected from the group consisting of a bisphenol A backbone, a bisphenol F backbone, a bisphenol A / F mixed backbone, a naphthalene backbone, a fluorene backbone, a biphenyl backbone, an anthracene backbone, a pyrene backbone, a xatonne backbone, an adamantane backbone, and a dicyclopentadiene backbone.

[0173] Among them, as an epoxy polymer, it is preferred to have at least one structure selected from the structure shown in formula (1) below (also called "structure (1)") and the structure shown in formula (2) below (also called "structure (2)").

[0174]

[0175] In equation (1), R 1 and R 2 Each represents an organic group, at least one of which is an organic group with a molecular weight of 16 or more. In formula (2), R 3 It represents a divalent cyclic organic group.

[0176] Furthermore, any "organic group" containing a carbon atom can be any group. Specifically, examples include alkyl, alkenyl, and aryl groups, which can also be substituted with halogen atoms, groups containing heteroatoms, or other hydrocarbon groups. The same applies below.

[0177] In the above formula (1), R 1 and R 2 At least one of them represents an organic group with a molecular weight of 16 or more, preferably 16 to 1,000, such as alkyl groups such as ethyl, propyl, butyl, pentyl, hexyl, and heptyl, phenyl, tolyl, xylyl, naphthyl, and fluorenyl. R 1 and R 2 All of them can be organic groups with a molecular weight of 16 or more, or one of them can be an organic group with a molecular weight of 16 or more and the other can be an organic group or hydrogen atom with a molecular weight of 15 or less. It is preferable that one of them is an organic group with a molecular weight of 16 or more and the other is an organic group with a molecular weight of 15 or less. In particular, from the viewpoint of making it easier to control the workability of the resin, such as viscosity, and the strength of the cured product, it is preferable that one of them is methyl and the other is phenyl.

[0178] In the above formula (2), R 3 The divalent cyclic organic group can be an aromatic ring structure such as a benzene ring structure, a naphthalene ring structure, or a fluorene ring structure, or an aliphatic ring structure such as cyclobutane, cyclopentane, or cyclohexane. In addition, they can also independently have substituents such as hydrocarbon groups or halogen atoms. The divalent bonding part can be a divalent group located on a single carbon atom or a divalent group located on different carbon atoms. Preferred examples include: divalent aromatic groups with 6 to 100 carbon atoms, and groups derived from cycloalkanes with 2 to 100 carbon atoms such as cyclopropane or cyclohexane. In particular, from the viewpoint of controlling the workability such as resin viscosity and the strength of the cured product, 3,3,5-trimethyl-1,1-cyclohexylene (also known as "structure (4)") shown in the following formula (4) is preferred.

[0179]

[0180] Furthermore, the epoxy polymer preferably has a fluorene skeleton as shown in formula (5). Due to the rigidity of the fluorene skeleton shown in formula (5), it exhibits excellent heat resistance and low linear expansion, and the molecular weight per unit is greater than that of ordinary epoxy compounds. As a result, the proportion of secondary hydroxyl groups, which are the cause of hygroscopicity, in the overall molecular structure is relatively low, thus exhibiting low hygroscopicity.

[0181]

[0182] In addition, epoxy polymers having the structure represented by the following formula (3) (also called "structure (3)") can be listed as epoxy polymers.

[0183]

[0184] In the above formula (3), R 4 R 5 R 6 R 7 Each of these is an organic group with a molecular weight of 15 or more. Alkyl groups with a molecular weight of 15 to 1,000 are preferred, especially from the viewpoint of controlling resin viscosity and other workability aspects, and the strength of the cured product. 4 R 5 R 6 R 7 All are methyl groups.

[0185] From the viewpoint of balancing the reduction of moisture absorption and the strength retention of the cured material and the thermally conductive sheet, the epoxy polymer is particularly preferred to be an epoxy polymer containing either structure (1) or structure (2) and structure (3).

[0186] Compared to typical epoxy polymers with bisphenol A and bisphenol F backbones, this epoxy polymer contains a large number of hydrophobic hydrocarbons and aromatic structures. Therefore, by formulating this epoxy polymer, the moisture absorption of this thermally conductive sheet as the resulting cured product can be reduced.

[0187] In addition, from the viewpoint of reducing moisture absorption, the epoxy polymer preferably contains a large number of structures (1), (2) and (3) as hydrophobic structures.

[0188] The mass-average molecular weight (Mw) of the epoxy polymer is preferably 5,000 or more, more preferably 10,000 or more, more preferably 15,000 or more, more preferably 20,000 or more, more preferably 25,000 or more, and more preferably 30,000 or more. As an upper limit, 100,000 or less can be listed. Within this range, there is a tendency to improve the film-forming properties of the composition of the present invention and the workability of the thermosetting sheet in its uncured state. Furthermore, the improved film-forming properties have the effect of connecting the fillers to each other in the uncured stage of the thermosetting sheet, thus reducing the likelihood of pore formation.

[0189] From the viewpoint of ensuring the film-forming properties and flexibility of the composition of the present invention, the epoxy equivalent of the epoxy polymer is preferably 5,000 g / equivalent or more, more preferably 7,000 g / equivalent or more, and even more preferably 8,000 g / equivalent or more. On the other hand, from the viewpoint of solubility in a solvent, it is preferably 25,000 g / equivalent or less, and even more preferably 20,000 g / equivalent or less.

[0190] In addition, the mass-average molecular weight (Mw) of epoxy polymers refers to the converted value of polystyrene determined by gel permeation chromatography.

[0191] In addition, epoxy equivalent is defined as "the mass of an epoxy polymer containing 1 equivalent of epoxy groups", which can be determined according to JIS K7236.

[0192] The above epoxy polymers can be used in combination, either one or more.

[0193] (Content of epoxy compounds)

[0194] The content of epoxy polymer is preferably 5% by mass or more and less than 30% by mass relative to the component (resin component) after removing solvent and inorganic filler from the composition of the present invention, in other words, relative to 100% by mass of the solid component after removing inorganic filler from the composition of the present invention.

[0195] By containing 5% by mass or more of epoxy polymer relative to 100% by mass of the solids after removing the inorganic filler from the composition of the present invention, film-forming properties can be maintained, which is therefore preferred. On the other hand, by containing epoxy polymer in a proportion of less than 30% by mass, the flexibility of the uncured thermosetting sheet can be maintained, which is also preferred.

[0196] From the above perspective, relative to 100% by mass of the solid content after removing the inorganic filler from the composition of the present invention, the content of epoxy polymer is preferably 5% by mass or more, more preferably 7.5% by mass or more, and more preferably 10% by mass or more. On the other hand, from the viewpoint of increasing the crosslinking density of the cured product, it is preferably less than 30% by mass, more preferably 27.5% by mass or less, more preferably 25% by mass or less, more preferably 24% by mass or less, more preferably 23% by mass or less, and more preferably 22% by mass or less.

[0197] The content of the polyfunctional epoxy compound is preferably 5% by mass or more and 95% by mass or less, relative to the composition after removing the solvent and inorganic filler from the composition of the present invention (resin component), in other words, relative to 100% by mass of the solid component after removing the inorganic filler from the composition of the present invention.

[0198] By including 5% by mass or more of the multifunctional epoxy compound, the crosslinking density of the cured product can be increased, which can improve, for example, the resistance to internal stress under high temperature, such as reflow soldering resistance and sintering resistance. On the other hand, by including 95% by mass or less, the amount of other components used to maintain the film-forming properties of the composition of the present invention can be ensured.

[0199] From the above perspective, relative to 100% by mass of the solid component after removing the inorganic filler from the composition of the present invention, the content of the polyfunctional epoxy compound is preferably 5% by mass or more, more preferably 10% by mass or more, and more preferably 15% by mass or more. On the other hand, it is preferably 95% by mass or less, and more preferably 90% by mass or less.

[0200] Of which, relative to 100% by mass of the solid component after removing the inorganic filler from the composition of the present invention, the content of a polyfunctional epoxy compound having three or more epoxy groups per molecule is preferably 5% by mass or more and 50% by mass or less.

[0201] If the content of a polyfunctional epoxy compound having three or more epoxy groups per molecule is 5% by mass or more, the crosslinking density of the cured product can be increased, and the storage modulus of the cured product can be maintained. Accordingly, its resistance to, for example, being subjected to internal stress or external force at high temperatures, as well as its resistance to reflow soldering and sintering, can be improved, which is therefore preferred. From the above viewpoint, relative to 100% by mass of the solid component after removing the inorganic filler from the composition of the present invention, the content of a polyfunctional epoxy compound having three or more epoxy groups per molecule is preferably 5% by mass or more, more preferably 7.5% by mass or more, and more preferably 10% by mass or more.

[0202] On the other hand, if the content of a polyfunctional epoxy compound having three or more epoxy groups per molecule is 50% by mass or less, the toughness of the uncured thermosetting sheet can be maintained, and the moisture absorption rate of the cured sheet can be suppressed, which is therefore preferable. From the above perspective, relative to 100% by mass of the solid component after removing the inorganic filler from the composition of the present invention, the content of a polyfunctional epoxy compound having three or more epoxy groups per molecule is preferably 50% by mass or less, more preferably 45% by mass or less, and more preferably 40% by mass or less.

[0203] From the viewpoint of adjusting the epoxy equivalent (WPE) of the resin component of the composition of the present invention to a suitable range, the content of a multifunctional epoxy compound having three or more epoxy groups per molecule and having an epoxy equivalent of 25 to 200 g / equivalent is preferably 5% by mass or more and 50% by mass or less, more preferably 7.5% by mass or more or 45% by mass or less, and more preferably 10% by mass or more or 40% by mass or less, from 10% by mass or more.

[0204] When using both epoxy polymers and multifunctional epoxy compounds, from the viewpoint of simultaneously improving the film-forming properties of the composition of the present invention and the elastic modulus of the sheet-cured product, the content of the multifunctional epoxy compound having three or more epoxy groups per molecule is preferably 20 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of epoxy polymer content. In particular, if the content of the multifunctional epoxy compound having three or more epoxy groups per molecule is 20 parts by mass or more, relative to 100 parts by mass of epoxy polymer content, the crosslinking density of the cured product can be increased, and its resistance to, for example, being subjected to internal stress or external force at high temperatures, such as reflow soldering resistance and sintering resistance, can be improved, which is therefore preferred.

[0205] From the above perspective, relative to the content of 100 parts by mass of epoxy polymer, the content of polyfunctional epoxy compound having 3 or more epoxy groups per molecule is preferably 20 parts by mass or more and 500 parts by mass or less, more preferably 30 parts by mass or more or 400 parts by mass or less, more preferably 40 parts by mass or more or 350 parts by mass or less, more preferably 60 parts by mass or more or 300 parts by mass or less, and more preferably 90 parts by mass or more or 200 parts by mass or less.

[0206] From the viewpoint of maintaining the film-forming properties of this thermosetting sheet, the content ratio of inorganic filler to epoxy polymer (epoxy polymer / inorganic filler) is preferably 0.01 or more, more preferably 0.02 or more, and more preferably 0.03 or more. On the other hand, from the viewpoint of improving the flexural strength of this thermosetting sheet in its uncured state, it is preferably less than 0.2, more preferably 0.15 or less, and more preferably 0.14 or less.

[0207] From the viewpoint of improving the retention force of the inorganic filler, the mass ratio of the inorganic filler to the polyfunctional epoxy compound having three or more epoxy groups per molecule (polyfunctional epoxy compound having three or more epoxy groups per molecule / inorganic filler) is preferably 0.02 or more, more preferably 0.03 or more, and more preferably 0.04 or more. On the other hand, from the viewpoint of improving the thermal conductivity of this thermally conductive sheet, it is preferably 0.2 or less, more preferably 0.18 or less, and more preferably 0.16 or less.

[0208] From the viewpoint of improving the operability of this thermosetting sheet, the mass ratio of inorganic filler to epoxy compound (epoxy compound / inorganic filler) is preferably 0.2 or more, further preferably 0.22 or more, and even more preferably 0.25 or more. On the other hand, from the viewpoint of improving the thermal conductivity of this thermally conductive sheet, it is preferably 0.6 or less, further preferably 0.57 or less, and even more preferably 0.55 or less.

[0209] (Other polymers with a molecular weight of 5,000 or higher)

[0210] The composition of the present invention may replace the above-mentioned epoxy polymer, or together with the above-mentioned epoxy polymer, contain a polymer other than the above-mentioned epoxy polymer with a mass-average molecular weight (Mw) of 5,000 or more (also referred to as "other polymers").

[0211] In this invention, epoxy polymers and other polymers are collectively referred to as "polymers".

[0212] By including this polymer in the composition of the present invention, film-forming properties can be improved even by increasing the proportion of boron nitride aggregate particles.

[0213] The other polymers mentioned can be any of thermoplastic resins and thermosetting resins.

[0214] Examples of thermoplastic and thermosetting resins include polyphenylene ether, polyphenylene sulfide, polyarylate, polysulfone, polyethersulfone, polyetheretherketone, or polyetherketone. Additionally, as the aforementioned thermoplastic and thermosetting resins, heat-resistant resins known as super engineering plastics, such as thermoplastic polyimides, thermosetting polyimides, benzoxazine, and reactants of polybenzoxazole and benzoxazine, can also be used. Furthermore, styrene-based polymers such as styrene and alkylstyrene, (meth)acrylate polymers such as alkyl methacrylate and glycidyl methacrylate, styrene-(meth)acrylate copolymers such as styrene-glycidyl methacrylate, polyvinyl alcohol derivatives such as polyvinyl butyral, polyvinyl alcohol benzaldehyde, and polyvinyl alcohol acetal, norbornene polymers containing norbornene compounds, and phenoxy resins can also be used. Among these, phenoxy resins are preferred from the perspectives of heat resistance and compatibility with thermosetting resins.

[0215] The aforementioned thermoplastic resin and thermosetting resin may be used individually or in combination with more than one. Either thermoplastic resin or thermosetting resin may be used, or both may be used in combination.

[0216] The content of polymers with a mass-average molecular weight (Mw) of 5,000 or more (the total content of epoxy polymers and other polymers) is preferably 5% by mass or more and less than 30% by mass relative to 100% by mass of the solid components after removing inorganic fillers from the composition of the present invention.

[0217] The inorganic filler retains its holding power and film-forming properties by containing 5% by mass or more of a polymer with a mass-average molecular weight (Mw) of 5,000 or more, and the strength during curing is maintained by containing the polymer in a proportion of less than 30% by mass, which is therefore preferred.

[0218] From the above perspective, the content of polymers with a mass-average molecular weight (Mw) of 5,000 or more, relative to 100% by mass of the solids after removing the inorganic filler from the composition of the present invention, is preferably 5% by mass or more, more preferably 7.5% by mass or more, and more preferably 10% by mass or more. On the other hand, it is preferably less than 30% by mass, more preferably 27.5% by mass or less, more preferably 25% by mass or less, more preferably 24% by mass or less, more preferably 23% by mass or less, and more preferably 20% by mass or less. From the viewpoint of maintaining the softness of the uncured sheet thermosetting composition and improving workability, it is more preferably 18% by mass or less.

[0219] In the above, the other polymers preferably have functional groups that react with the epoxy compound.

[0220] Here, functional groups that react with the epoxy compound, for example, functional groups that react with epoxy groups, can be listed as: phenolic hydroxyl groups, epoxy groups, carboxylic acid groups, carboxylic anhydride groups, active esters, etc.

[0221] <Curing agent>

[0222] The compositions of the present invention preferably contain a curing agent, if desired.

[0223] Examples of curing agents include: phenolic resins, compounds with a nitrogen-containing heterocyclic structure (also known as "nitrogen-containing heterocyclic compounds"), acid anhydrides with an aromatic or alicyclic skeletons, hydrides of such acid anhydrides, or modifications of such acid anhydrides.

[0224] One type of curing agent can be used, or two or more can be used together.

[0225] By using these preferred curing agents, a cured product with an excellent balance of heat resistance, moisture resistance and electrical properties can be obtained.

[0226] When the composition of the present invention contains the aforementioned epoxy compound as a thermosetting compound, it is preferable to use a curing agent having active groups capable of reacting with epoxy groups. For example, it is preferable to use at least one of phenolic resin, benzoxazine compound, polyarylate, cyanate ester, and maleimide in combination with the epoxy compound. That is, the composition of the present invention preferably contains an epoxy compound and at least one of phenolic resin, benzoxazine compound, polyarylate, cyanate ester, and maleimide. From the viewpoint of increasing crosslinking density and adjusting crosslinking speed while maintaining heat resistance, it is preferable to contain both an epoxy compound and a phenolic resin. Furthermore, from the viewpoint of suppressing the decrease in thermal conductivity at high temperatures, it is preferable to contain an epoxy compound and a benzoxazine compound together with the phenolic resin.

[0227] (Phenolic resin)

[0228] Examples of phenolic resins include: phenolic varnish, o-cresol varnish, p-cresol varnish, tert-butylphenol varnish, dicyclopentadiene cresol, poly(p-vinylphenol), bisphenol A type phenolic varnish, diphenylmethyl modified phenolic varnish, decahydronaphthalene modified phenolic varnish, poly(di-o-hydroxyphenyl)methane, poly(di-m-hydroxyphenyl)methane, or poly(di-p-hydroxyphenyl)methane. To further improve the flexibility of the composition, the cured product, and the thermally conductive sheet of the present invention, or to improve the mechanical properties and heat resistance of the cured product, phenolic varnish-type phenolic resins with a rigid main chain backbone or phenolic resins with a triazine backbone are preferred. Furthermore, to improve the flexibility of the uncured thermosetting sheet and the toughness of the cured product, allyl phenolic resins are preferred. By including phenolic resins, the curing speed of the epoxy compound is increased, residual groups are suppressed to a smaller extent, thereby effectively improving heat resistance.

[0229] (Benzoxazine compounds)

[0230] The benzoxazine compound is a cross-linked and cured compound obtained by heating, and also functions as a curing agent for the epoxy compound. Therefore, by combining the epoxy compound and the benzoxazine compound, the hydroxyl groups generated during the cross-linking of the benzoxazine compound react with the epoxy groups of the epoxy compound to form bonds. Thus, the cross-linked structure formed by the epoxy compound and the cross-linked structure formed by the benzoxazine compound are combined to create a more robust cross-linked structure, which increases the glass transition temperature (Tg) of the cured product and further enhances its heat resistance.

[0231] Benzoxazine compounds preferably have the structure shown in formula (I) or formula (II) below.

[0232]

[0233]

[0234] In formula (I), a represents an integer from 0 to 3, preferably 0 or 1, and more preferably 0.

[0235] R1 and R2 represent hydrogen atoms or monovalent organic groups, respectively.

[0236] Specific examples of R1 include: hydrogen atom, alkyl, alkenyl, cycloalkyl, aryl, aralkyl, alkynyl, etc. R1 can be substituted by any substituent.

[0237] Specific examples of R2 include: aliphatic hydrocarbon groups, aromatic hydrocarbon groups, etc.

[0238] * indicates a bond with other chemical structures.

[0239] In formula (II), b represents an integer from 0 to 4, preferably 0 or 1, and more preferably 0.

[0240] R3 represents a hydrogen atom or a monovalent organic group. When b is 2 or more, multiple R3s can be the same or different.

[0241] Specific examples of R3 include: aliphatic hydrocarbon groups, aromatic hydrocarbon groups, etc.

[0242] * indicates a bond with other chemical structures.

[0243] The benzoxazine compound preferably has a plurality of structures represented by formula (I) and / or formula (II) in one molecule. More specifically, the benzoxazine compound preferably has 2 to 4, more preferably 2 structures represented by formula (I) and / or formula (II) in one molecule. It is believed that by using such benzoxazine compounds, the curing properties and heat resistance can be further improved.

[0244] The benzoxazine compounds preferably include those represented by formula (III). The benzoxazine compounds represented by formula (III) are also commonly referred to as Pd-type benzoxazines.

[0245]

[0246] In equation (III), X 2 It is a single bond or a divalent linker.

[0247] More specifically, X 2 It can be a single bond, a straight-chain or branched alkylene group with 1 to 10 carbon atoms, -O-, -SO2-, -CO-, or a structure formed by connecting two or more of them.

[0248] Benzoxazine compounds may include those represented by formula (IV) below. Incidentally, benzoxazine compounds represented by formula (IV) below are also commonly referred to as Fa-type benzoxazines.

[0249] In equation (IV), X 2 Definition, specific examples and X in equation (III) above 2 same.

[0250]

[0251] Benzoxazine compounds include benzoxazine compounds that are solid at 25°C and benzoxazine compounds that are liquid at 25°C, but from the viewpoint of improving the glass transition temperature (Tg) of the compositions of the present invention and their cured products to improve heat resistance, benzoxazine compounds that are solid at 25°C are more preferred.

[0252] The content of benzoxazine compound is preferably 3% by mass or more and 50% by mass or less, more preferably 5% by mass or more or 30% by mass or less, and more preferably 7% by mass or more or 25% by mass or less, relative to 100% by mass of the solid component after removing the inorganic filler from the composition of the present invention.

[0253] When the proportion of benzoxazine compounds increases, the film becomes brittle during film formation, potentially reducing its film-forming properties. Therefore, the content of benzoxazine compounds in the composition of the present invention is preferably less than the content of epoxy compounds. Specifically, the mass ratio (benzoxazine compound / epoxy compound) of the benzoxazine compound content to the epoxy compound content in the solid component after removing the inorganic filler from the composition of the present invention is preferably less than 0.8, preferably 0.7 or less, preferably 0.6 or less, and preferably 0.5 or less. On the other hand, from the viewpoint of improving heat resistance, this mass ratio is preferably 0.05 or more, more preferably 0.07 or more, and more preferably 0.08 or more.

[0254] (Polyaryl ester)

[0255] By incorporating an epoxy compound and a polyaryl ester, the ester groups or terminal hydroxyl groups in the main chain backbone of the polyaryl ester react with the epoxy groups of the epoxy compound to form a bond. Therefore, the cross-linked structure formed by the epoxy compound is composited with the cross-linked structure formed by the reaction of the epoxy compound and the polyaryl ester, resulting in a more robust cross-linked structure. Consequently, the glass transition temperature (Tg) of the composition of the present invention can be increased, resulting in excellent heat resistance, for example, suppressing changes in the elastic modulus of the cured product at high temperatures.

[0256] Examples of such polyarylates include compounds represented by formula (A).

[0257]

[0258] In formula (A) above, X can be a hydrogen atom group, an aliphatic group, or an aromatic group independently. Specifically, examples include: hydrogen atoms, substituted or unsubstituted alkyl groups, aryl groups, etc.

[0259] Y is an independent single bond, -CR 1 R 2 -, O, CO, or S are all acceptable. Furthermore, the R... 1 R 2 Each can independently represent a hydrogen atom, a methyl group, or an ethyl group, or represent R. 1 With R 2 Cyclohexylenes formed by bonding. Examples include straight-chain, branched, or cyclic alkylene groups with 1 to 12 carbon atoms.

[0260] Z can be independently represented by a hydrogen atom, a hydroxyl group, or an alkoxy group.

[0261] n is a repeating number, which can be any integer greater than or equal to 1. For example, it is preferably an integer from 1 to 100, and even more preferably an integer greater than or equal to 1 or less than 90, and even more preferably an integer greater than or equal to 2 or less than 80.

[0262] From the viewpoint of improving heat resistance, the molecular weight of the polyarylate is preferably 500 or more, more preferably 700 or more, and even more preferably 1,000 or more. On the other hand, from the viewpoint of resin flowability, it is preferably 10,000 or less, more preferably 8,000 or less, and even more preferably 5,000 or less.

[0263] From the viewpoint of dimensional stability at high temperatures, the glass transition temperature of the polyarylate is preferably 80°C or higher, more preferably 100°C or higher, and even more preferably 120°C or higher. On the other hand, from the viewpoint of improving toughness, it is preferably 300°C or lower, more preferably 270°C or lower, and even more preferably 250°C or lower.

[0264] From the viewpoint of reducing hygroscopicity, the functional group equivalent (amount of hydroxyl and ester groups) of the polyaryl ester is preferably 100 g / equivalent or more, more preferably 120 g / equivalent or more, and more preferably 140 g / equivalent or more. On the other hand, from the viewpoint of improving heat resistance, it is preferably 1000 g / equivalent or less, more preferably 800 g / equivalent or less, and more preferably 600 g / equivalent or less.

[0265] (cyanate ester)

[0266] As the cyanate ester, for example, it is a compound having an intramolecular -OCN group, as long as the -OCN group reacts upon heating. Specifically, examples include: 1,3-dicyanophenyl, 1,4-dicyanophenyl, 1,3,5-tricyanophenyl, 1,3-dicyanonaphthalene, 1,4-dicyanonaphthalene, 1,6-dicyanonaphthalene, 1,8-dicyanonaphthalene, 2,6-dicyanonaphthalene, 2,7-dicyanonaphthalene, 1,3,6-tricyanonaphthalene, 4,4'-dicyanobiphenyl, bis(4-cyanophenyl)methane, bis(3,5-dimethyl-4-cyanophenyl)methane, 2,2-bis( 4-Cyanophenyl)propane, 2,2-bis(3,5-dibromo-4-cyanophenyl)propane, bis(4-cyanophenyl) ether, bis(4-cyanophenyl) sulfide, bis(4-cyanophenyl) sulfone, tris(4-cyanophenyl) phosphite, tris(4-cyanophenyl) phosphate, and cyanate esters obtained by reacting phenolic varnish resin with cyanide halide, etc., can also use prepolymers with triazine rings formed by trimerizing the cyanate groups of these polyfunctional cyanate esters.

[0267] (maleimide)

[0268] The maleimide can be any compound having one or more, preferably two or more, maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrole-1-yl) in one molecule.

[0269] In addition to forming bonds with epoxides in the presence of a suitable catalyst, maleimides can also undergo free radical polymerization based on the olefinic carbon-carbon unsaturated bonds contained in the maleimide group. Therefore, maleimides can also bond with each other.

[0270] As a maleimide, it can be, for example, an aliphatic maleimide containing an aliphatic amine skeleton, or an aromatic maleimide containing an aromatic amine skeleton.

[0271] (Content of curing agent)

[0272] The curing agent is preferably contained in a proportion of 1% or more and 50% or less of the solid components after removing the inorganic filler from the composition of the present invention, more preferably in a proportion of 3% or more or 40% or less of the solid components, more preferably in a proportion of 5% or more or 30% or less of the solid components, and more preferably in a proportion of 10% or more or 25% or less of the solid components.

[0273] When the content of the curing agent is above the lower limit mentioned above, the reaction proceeds effectively and sufficient curing performance can be obtained. When the content of the curing agent is below the upper limit mentioned above, the crosslinking density can be increased, thus increasing the strength, which is preferred.

[0274] <Curing Accelerator>

[0275] The composition of the present invention may contain a thermosetting catalyst as a curing accelerator as needed, in order to adjust the curing speed, the physical properties of the cured product, etc.

[0276] The thermosetting catalyst is preferably selected appropriately based on the type of thermosetting compound and curing agent.

[0277] Specific examples of thermosetting catalysts include: chain or cyclic tertiary amines, organophosphorus compounds, diazabicyclic alkenes such as quaternary phosphonium salts or organic acid salts, and imidazoles. Additionally, organometallic compounds, quaternary ammonium salts, or metal halides can also be used.

[0278] Examples of organometallic compounds mentioned above include zinc octoate, tin octoate, or aluminum acetylacetonate complexes.

[0279] Furthermore, the nitrogen-containing heterocyclic compound described as a curing agent also functions as a thermosetting catalyst, and therefore can be formulated as a thermosetting catalyst.

[0280] In particular, from the viewpoints of storage stability, heat resistance and curing speed, thermosetting catalysts are preferably compounds containing imidazole (also known as "imidazole compounds").

[0281] Preferred imidazole compounds include, for example: 2-ethyl-4-methylimidazolium, 2-phenylimidazolium, 1-benzyl-2-methylimidazolium, 1-benzyl-2-phenylimidazolium, 1-cyanoethyl-2-undecylimidazolium, 1-cyanoethyl-2-ethyl-4-methylimidazolium, 2-phenyl-4-methylimidazolium, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-triazine, 2, 4-Diamino-6-[2'-Undecylimidazolyl-(1')]-ethyl-triazine, 2,4-Diamino-6-[2'-ethyl-4-methylimidazolyl-(1')]-ethyl-triazine, 2,4-Diamino-6-[2'-methylimidazolyl-(1')]-ethyl-triazine isocyanuric acid adduct, 2-phenylimidazolyl isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazolium, 2-phenyl-4-methyl-5-hydroxymethylimidazolium, etc.

[0282] In particular, by using imidazole compounds with a melting point of 100°C or higher, and more preferably 200°C or higher, it is possible to obtain this cured product with excellent storage stability and sealing properties.

[0283] Furthermore, from the viewpoint of adhesion, it is more preferable to include nitrogen-containing heterocyclic compounds other than the imidazole ring.

[0284] In addition, thermosetting catalysts can be used alone or in combination of two or more.

[0285] By using two or more imidazole compounds with a melting point of 100°C or higher, the composition of the present invention exhibits excellent storage stability, and the cured product exhibits excellent heat resistance. In particular, among the two or more imidazole compounds, at least one is more preferably a melting point of 200°C or higher, and even more preferably two or more have a melting point of 200°C or higher.

[0286] The thermosetting catalyst is preferably contained in 0.1% by mass and 10% by mass or less of the solid component after removing the inorganic filler from the composition of the present invention, and more preferably in 0.1% by mass and 5% by mass or less.

[0287] When the content of the thermosetting catalyst is above the lower limit, it can sufficiently promote the curing reaction and achieve good curing. When the content of the thermosetting catalyst is below the upper limit, the curing speed will not be too fast. Therefore, the composition of the present invention can have good storage stability.

[0288] <Inorganic packing>

[0289] The inorganic filler contained in the composition of the present invention is preferably an inorganic filler with a thermal conductivity of 2.0 W / m·K or higher, particularly preferably 3.0 W / m·K or higher, particularly preferably 5.0 W / m·K or higher, and particularly preferably 10.0 W / m·K or higher.

[0290] Examples of inorganic fillers include: electrically insulating fillers formed solely of carbon; and fillers formed of metal carbides or half-metal carbides, metal oxides or half-metal oxides, and metal nitrides or half-metal nitrides.

[0291] Examples of electrically insulating fillers formed solely of carbon include diamond (thermal conductivity: approximately 2000 W / m·K).

[0292] Examples of metal carbides or semi-metal carbides include silicon carbide (thermal conductivity: about 60 to 270 W / m·K), titanium carbide (thermal conductivity: about 21 W / m·K), and tungsten carbide (thermal conductivity: about 120 W / m·K).

[0293] Examples of the metal oxides or semi-metal oxides mentioned above include: magnesium oxide (thermal conductivity: about 40 W / m·K), aluminum oxide (thermal conductivity: about 20 to 35 W / m·K), zinc oxide (thermal conductivity: about 54 W / m·K), yttrium oxide (thermal conductivity: about 27 W / m·K), zirconium oxide (thermal conductivity: about 3 W / m·K), ytterbium oxide (thermal conductivity: about 38.5 W / m·K), beryllium oxide (thermal conductivity: about 250 W / m·K), and silane (a ceramic formed from silicon, aluminum, oxygen, and nitrogen, with a thermal conductivity of about 21 W / m·K).

[0294] Examples of the metal nitrides or half-metal nitrides include: boron nitride (thermal conductivity in the face direction of plate-shaped particles of hexagonal boron nitride (h-BN): about 200 to 500 W / m·K), aluminum nitride (thermal conductivity: about 160 to 285 W / m·K), silicon nitride (thermal conductivity: about 30 to 80 W / m·K), etc.

[0295] These inorganic fillers can be used in single-origin or in combination of two or more.

[0296] From the perspective of electrical insulation, the volume resistivity of inorganic fillers at 20℃ is preferably 10. 13 Ω・cm or more, especially more preferably 10 14Ω·cm or higher. Among these, metal oxides, half-metal oxides, metal nitrides, or half-metal nitrides are preferred from the perspective of easily ensuring sufficient electrical insulation of the thermally conductive sheet. Specifically, examples of such inorganic fillers include: alumina (Al₂O₃, volume resistivity: >10 Ω·cm). 14 Ω・cm), aluminum nitride (AlN, volume resistivity: >10 14 Ω・cm), boron nitride (BN, volume resistivity: >10 14 Ω・cm), silicon nitride (Si3N4, volume resistivity: >10 14 Ω・cm), silicon dioxide (SiO2, volume resistivity: >10 14 Ω・cm), etc.

[0297] Among them, aluminum oxide, aluminum nitride, and boron nitride are preferred, and aluminum oxide and boron nitride are particularly preferred from the perspective of giving the thermally conductive sheet high insulation properties.

[0298] Inorganic fillers can be in the form of amorphous particles, spheres, whiskers, fibers, plates, or aggregates or mixtures thereof.

[0299] Furthermore, in this invention, "spherical" generally refers to a length-to-diameter ratio (the ratio of the major diameter to the minor diameter) of 1 or more and 2 or less, preferably 1 or more and 1.75 or less, more preferably 1 or more and 1.5 or less, and even more preferably 1 or more and 1.4 or less.

[0300] The aspect ratio can be determined as follows: from an image obtained by taking a cross-section of the composition of the present invention or the thermally conductive sheet using a scanning electron microscope (SEM), arbitrarily select more than 10 particles, determine the aspect ratio of each particle, and calculate the average value.

[0301] (Boron nitride aggregate particles)

[0302] Considering the advantages of minimal moisture absorption and low toxicity when the composition of the present invention is formed into a sheet and cured (i.e., when the sheet-like cured product is produced), the efficient improvement of thermal conductivity, and the ability to impart high insulation to the thermally conductive sheet, the inorganic filler contained in the composition of the present invention is preferably "boron nitride aggregated particles" formed by the aggregation of primary boron nitride particles. That is, the composition of the present invention preferably contains boron nitride aggregated particles as the inorganic filler.

[0303] Alternatively, boron nitride aggregates can be used in combination with other inorganic fillers. However, the heat transfer behavior in this thermally conductive sheet, as described later, does not solely depend on the thermal conductivity within the inorganic filler. Therefore, even when using diamond particles or similar materials with extremely high thermal conductivity but also very high cost among the inorganic fillers exemplified above, the thermal conductivity in the thickness direction of this thermally conductive sheet will not increase drastically. Therefore, the use of boron nitride aggregates and other inorganic fillers is primarily aimed at reducing the cost of the composition of the present invention. Therefore, considering relatively low cost and relatively high thermal conductivity, magnesium oxide, aluminum oxide, tungsten carbide, silicon carbide, aluminum nitride, etc., are preferably appropriately selected as inorganic fillers used in combination with boron nitride aggregates, with aluminum oxide being more preferred.

[0304] From the viewpoint of high thermal conductivity, it is preferable that the boron nitride aggregated particles account for 75% or more of the inorganic filler contained in the composition of the present invention, preferably 80% or more of the boron nitride aggregated particles, and preferably 85% or more of the boron nitride aggregated particles (including 100% by mass).

[0305] The preferred shape of the boron nitride aggregate particles is spherical.

[0306] From the perspective of improving thermal conductivity, the preferred aggregation structure of boron nitride aggregates is a carding structure.

[0307] Furthermore, the aggregate structure of boron nitride aggregates can be confirmed by scanning electron microscopy (SEM).

[0308] The term "ka-ya structure" refers to a structure in which plate-like particles are stacked in a complex manner without orientation, as described in "Ceramics・43・No.2" (issued by the Japan Ceramic Association in 2008).

[0309] More specifically, a cardboard structure refers to a structure in which the planar portion of a primary particle forming an aggregate contacts the end faces of other primary particles present within that aggregate. Figure 1 A schematic diagram of the cardboard box structure is shown.

[0310] The aggregated particles with the cardioid structure have very high structural breaking strength and will not break during the pressing process in the sheet forming of this thermally conductive sheet. Therefore, it is possible to have primary particles, which are normally oriented along the length of this thermally conductive sheet, exist in random directions. Therefore, when using aggregated particles with a cardioid structure, the proportion of the ab plane of the primary particles oriented along the thickness direction of this thermally conductive sheet can be further increased, thus enabling effective heat conduction in the thickness direction and further improving the thermal conductivity in the thickness direction.

[0311] Furthermore, boron nitride aggregates with a carousel structure can be manufactured, for example, by the method described in International Publication No. 2015 / 119198.

[0312] When using boron nitride aggregates with a carousel structure, the particles can be surface-treated with a surface treatment agent.

[0313] As a surface treatment agent, known surface treatment agents such as silane coupling treatment can be used. It is believed that by using chemical treatment to improve the interfacial tightness between the inorganic filler and the thermosetting compound, i.e., the matrix resin, the thermal conductivity at the interface can be further reduced.

[0314] Furthermore, in the compositions of the present invention, the thermosetting compound is also referred to as a "matrix resin" in consideration of its role in encapsulating the inorganic filler and maintaining the overall shape of the compositions of the present invention.

[0315] By using aggregated particles formed from primary particle aggregation as inorganic fillers in the compositions of this invention, the particle size can be increased compared to inorganic fillers that directly use primary particles.

[0316] By increasing the particle size of inorganic fillers, the heat transfer path between inorganic fillers through thermosetting compounds with low thermal conductivity can be reduced, thus reducing the increase in thermal resistance in the thickness direction of the heat transfer path.

[0317] From the above perspective, the lower limit of the maximum particle size of boron nitride aggregates is preferably 20 μm or more, more preferably 30 μm or more, and even more preferably 40 μm or more. On the other hand, the upper limit of the maximum particle size is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, and even more preferably 90 μm or less.

[0318] Furthermore, the average particle size of the boron nitride aggregates is not particularly limited. Preferably, it is 5 μm or more, more preferably 10 μm or more, and particularly preferably 15 μm or more. Also, it is preferably 100 μm or less, more preferably 90 μm or less. Because the average particle size of the boron nitride aggregates is 5 μm or more, the number of particles in the composition and cured product of the present invention is relatively small, thus reducing the interparticle interfaces and consequently decreasing the thermal resistance, resulting in a high thermal conductivity sheet. Furthermore, when the average particle size is below the aforementioned upper limit, there is a tendency to obtain a smooth surface in the cured product.

[0319] When the average or maximum particle size of the boron nitride aggregates is below the aforementioned upper limit, a high-quality film without surface roughness can be formed when the thermosetting compound, i.e., the matrix resin, contains boron nitride aggregates. When the average or maximum particle size is above the aforementioned lower limit, the interface between the matrix resin and the boron nitride aggregates is reduced, resulting in lower thermal resistance, high thermal conductivity, and achieving the sufficient improvement in thermal conductivity required for thermally conductive sheets in power semiconductor devices as an inorganic filler.

[0320] Furthermore, the influence of the interfacial thermal resistance between the matrix resin and the boron nitride aggregates becomes significant when the size of the boron nitride aggregates is less than 1 / 10 of the thickness of the thermally conductive sheet. Especially in the case of power semiconductor devices, since thermally conductive sheets with a thickness of 100 μm to 300 μm are commonly used, from a thermal conductivity point of view, it is also preferable that the maximum particle size of the boron nitride aggregates is greater than the aforementioned lower limit.

[0321] In addition, by having the maximum particle size of the boron nitride aggregates be above the aforementioned lower limit, not only can the increase in thermal resistance caused by the interface between the boron nitride aggregates and the matrix resin be suppressed, but the number of thermal conduction paths between the particles required is also reduced, and the probability of thermally conductively connecting one side to another in the thickness direction of this thermally conductive sheet is increased.

[0322] On the other hand, by keeping the maximum particle size of the boron nitride aggregates below the aforementioned upper limit, the protrusion of the boron nitride aggregates onto the surface of this thermally conductive sheet can be suppressed, resulting in a good surface shape without surface roughness. Therefore, for example, when manufacturing a sheet that is bonded to a copper substrate, it has sufficient adhesion and can obtain excellent voltage resistance characteristics.

[0323] The ratio of the size (maximum particle size) of the boron nitride aggregates to the thickness of the thermally conductive sheet (maximum particle size / thickness) is preferably 0.3 or more and 1.0 or less, more preferably 0.35 or more or 0.95 or less, and more preferably 0.4 or more or 0.9 or less.

[0324] Furthermore, the maximum and average particle size of boron nitride aggregates can be determined, for example, by the following methods.

[0325] Regarding the maximum and average particle size of the boron nitride aggregates used as raw materials, the particle size distribution can be measured using a laser diffraction / scattering particle size distribution measuring device for samples obtained by dispersing boron nitride aggregates in a solvent, specifically samples obtained by dispersing boron nitride aggregates in a pure water medium containing a dispersing stabilizer. Based on the obtained particle size distribution, the maximum particle size Dmax and average particle size D50 of the boron nitride aggregates can be determined.

[0326] Here, Dmax and D50 are the maximum particle size and the cumulative 50% particle size in the volume-based particle size distribution obtained by laser diffraction scattering particle size distribution determination method.

[0327] Alternatively, the maximum and average particle size can be determined using a dry particle size distribution measuring device such as the Morphologi G3 (manufactured by Malvern).

[0328] On the other hand, the maximum and average particle size of the boron nitride aggregates in the composition of the present invention or the thermally conductive sheet can also be determined by physically removing organic components such as thermosetting compounds by dissolving them in a solvent (including a heated solvent), or by allowing them to swell to reduce their adhesion strength to the boron nitride aggregates, and then removing them by heating the organic components under atmospheric conditions to ashing them. The maximum particle size Dmax and average particle size D50 can then be determined using the same method as described above.

[0329] In addition, regarding the maximum particle size of the boron nitride aggregates in the composition of the present invention or the thermally conductive sheet, the maximum particle size can be determined by directly observing more than 10 arbitrary boron nitride aggregates in the cross-section of the composition of the present invention or the thermally conductive sheet using a scanning electron microscope, transmission electron microscope, micro Raman spectrometer, atomic force microscope, etc.

[0330] In addition, the average particle size of the boron nitride aggregates in the composition of the present invention or the thermally conductive sheet can also be determined by directly observing more than 10 arbitrary boron nitride aggregates in the cross-section of the composition of the present invention or the thermally conductive sheet using a scanning electron microscope, transmission electron microscope, micro Raman spectrometer, atomic force microscope, etc., and by calculating the arithmetic mean of the particle diameters.

[0331] In addition, when the particles are non-spherical, the longest and shortest diameters are measured, and their average value is taken as the particle size.

[0332] (Content of inorganic filler)

[0333] Relative to 100% by mass of the solid components in the composition of the present invention, i.e., 100% by mass of the solid components of the entire composition, the content of inorganic filler is preferably 30% by mass or more and less than 90% by mass.

[0334] If the content of the inorganic filler is 30% by mass or more relative to 100% by mass of the solid components in the composition of the present invention, the insulation and thermal conductivity can be improved. From the above viewpoint, the content of the inorganic filler is preferably 30% by mass or more relative to 100% by mass of the solid components in the composition of the present invention, more preferably 40% by mass or more, more preferably 50% by mass or more, and more preferably 60% by mass or more. From the viewpoint of further improving thermal conductivity, it is even more preferably 65% ​​by mass or more.

[0335] On the other hand, if the content is less than 90% by mass, operability and film-forming properties can be maintained. From the above perspective, the content of the inorganic filler is preferably less than 90% by mass, more preferably 85% by mass or less, more preferably 80% by mass or less, and more preferably 75% by mass or less.

[0336] The content of the boron nitride aggregate particles is preferably 50% or more by mass relative to 100% of all inorganic fillers.

[0337] If the content of the boron nitride particles is 50% or more relative to 100% of the total inorganic filler, the insulation and thermal conductivity can be improved.

[0338] From the above perspective, the content of the boron nitride aggregate particles is preferably 50% by mass or more, more preferably 60% by mass or more, and more preferably 70% by mass or more, relative to 100% by mass of all inorganic fillers.

[0339] Solvent

[0340] The compositions of the present invention may contain an organic solvent as a solvent as needed, for example, to improve the coatability of a sheet-like cured product formed by a coating process.

[0341] Examples of organic solvents that may be contained in the compositions of the present invention include: methyl ethyl ketone, cyclohexanone, propylene glycol monomethyl ether acetate, butyl acetate, isobutyl acetate, propylene glycol monomethyl ether, etc. Only one of these organic solvents may be used, or two or more may be used in combination.

[0342] When the composition of the present invention contains an organic solvent, its content is appropriately determined based on factors such as operability during the manufacture of the thermally conductive sheet. Generally, the organic solvent is preferably used in such a way that the concentration of the solid components (total components other than the solvent) in the composition of the present invention is 10% by mass or more and 90% by mass or less, and particularly preferably in a way that is 40% by mass or more or 80% by mass or less.

[0343] Furthermore, when the composition of the present invention is formed into a sheet, the organic solvent is preferably used in such a manner that the concentration of the solid components (the total of the components other than the solvent) in the composition of the present invention is 95% by mass or more, more preferably 97% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more.

[0344] <Other Ingredients>

[0345] In addition to the above-mentioned components, the compositions of the present invention may also contain other components.

[0346] Other components may include, for example: dispersants, thermoplastic resins, organic fillers, additives such as silane coupling agents that improve the interfacial adhesion strength between inorganic fillers and resin components, additives that are expected to improve the adhesion strength between the thermally conductive sheet and conductive materials such as metal plates and circuit boards, insulating carbon components such as reducing agents, viscosity modifiers, thixotropic agents, flame retardants, colorants, various antioxidants such as phosphorus-based and phenolic-based antioxidants, process stabilizers such as phenolic acrylate-based stabilizers, heat stabilizers, hindered amine free radical scavengers (HAAS), impact modifiers, processing aids, metal passivators, copper damage preventers, antistatic agents, and extenders.

[0347] When using these additives, the amount added is generally sufficient as long as it is within the range required for these purposes.

[0348] (Silane coupling agent)

[0349] The compositions of the present invention preferably contain a silane coupling agent as needed.

[0350] By adjusting the silane coupling agent, the interfacial bonding strength between the inorganic filler and the thermosetting compound can be improved, and the composition of the present invention can suppress porosity and maintain insulation resistance and stability during curing.

[0351] Examples of silane coupling agents include: N-phenylγ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, p-styryltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane. One of these agents can be used alone, or two or more can be used in combination.

[0352] From the viewpoint of improving the interfacial adhesion between the inorganic filler and the thermosetting compound, the content of the silane coupling agent is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, more preferably 0.15 parts by mass or more, and more preferably 0.18 parts by mass or more, relative to 100 parts by mass of all inorganic filler. On the other hand, from the viewpoint of maintaining heat resistance, it is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and more preferably 1 part by mass or less, relative to 100 parts by mass of all inorganic filler.

[0353] <<Uses of the Compositions of the Invention>>

[0354] The compositions of the present invention can be cured by heating.

[0355] Furthermore, by molding the composition of the present invention into a sheet, this thermosetting sheet can be produced; by curing this thermosetting sheet, this sheet-shaped cured product can be formed and can be used as this thermally conductive sheet.

[0356] Furthermore, this cured material and this thermally conductive sheet can be used for a variety of applications. For example, they can be used as components of composite molded bodies, heat dissipation laminates, heat dissipation circuit boards, and power semiconductor devices, as described later. However, they are not limited to these applications.

[0357] <Manufacturing Method of This Thermosetting Sheet>

[0358] Next, an example of the manufacturing method of this thermosetting sheet will be described.

[0359] This thermosetting sheet can be obtained by the following method: forming the composition of the present invention into a sheet (this process is also called the "film forming process"), drying it as needed (this process is also called the "drying process"), subjecting it to low-temperature curing at a temperature below 0°C as needed (this process is also called the "low-temperature curing process"), and further pressurizing it as needed (this process is also called the "pressurizing process").

[0360] As an example of the manufacturing method of this thermosetting sheet, the manufacturing method is characterized by forming the composition of the present invention into a film and subjecting it to low-temperature curing at an ambient temperature below 0°C.

[0361] However, the order of the processes can be changed appropriately. For example, a low-temperature curing process can be performed after the pressurization process.

[0362] (Film-making process)

[0363] For example, a slurry-like composition of the present invention is prepared by mixing a thermosetting compound and an inorganic filler, as well as other components (raw materials) as needed, adding the solvent as needed, and kneading. This slurry-like composition of the present invention can be formed into a sheet by methods such as doctor blade coating, solvent casting, or extrusion film forming.

[0364] When the film is formed into a sheet using the above coating method, a slurry-like composition of the present invention is first coated onto the surface of a substrate to form a coating film. That is, a slurry-like composition of the present invention is used to form a coating film on a substrate by dip coating, spin coating, spray coating, doctor blade coating, or any other method.

[0365] In the coating of the slurry-like composition of the present invention, coating apparatus such as spin coaters, slot coaters, die coaters, and doctor blade coaters can be used. With such coating apparatus, a coating film of a specified thickness can be uniformly formed on the substrate.

[0366] In addition, copper plates or copper foils, or PET films, are commonly used as substrates, but there are no limitations.

[0367] (Drying process)

[0368] For the compositions of the present invention that are film-formed into sheets as described above, in order to remove solvents and low molecular weight components, drying is typically performed at a temperature (heating atmosphere temperature) of 10 to 150°C, wherein 25°C or higher or 120°C or lower, wherein 30°C or higher or 110°C or lower, wherein 100°C or lower.

[0369] When the drying temperature is below the upper limit mentioned above, the curing of the resin in the composition of the present invention is suppressed, and the resin in the sheet-like composition of the present invention tends to flow easily and remove pores during the subsequent pressurization process. When the drying temperature is above the lower limit mentioned above, the solvent tends to be removed effectively, and the productivity is improved.

[0370] The drying time is not particularly limited and can be appropriately adjusted according to the state of the composition, drying environment, etc., according to the present invention. The drying time is preferably 1 minute or more, more preferably 2 minutes or more, and even more preferably 5 minutes or more. The drying time is preferably 24 hours or less, more preferably 10 hours or less, even more preferably 4 hours or less, and particularly preferably 2 hours or less.

[0371] By drying for a time above the lower limit mentioned above, the solvent can be sufficiently removed, and the tendency for residual solvent to form pores within the cured sheet can be suppressed. By drying for a time below the upper limit mentioned above, productivity can be increased, and manufacturing costs can be reduced.

[0372] (Low-temperature curing process)

[0373] Next, it is preferable to perform low-temperature curing by placing the sheet-like composition of the present invention, as shaped as described above, in a temperature environment below 0°C.

[0374] By subjecting the sheet-like composition of the present invention to such low-temperature curing, the moisture inside the sheet can be frozen and dispersed in the form of tiny ice crystals. After returning to room temperature, moisture chambers sealed in tiny spaces are formed, thereby preventing insulation deterioration without creating large pores and suppressing cracking when the sheet is bent.

[0375] Since the faster the cooling rate during low-temperature curing, the more likely it is to form tiny ice crystals, a lower temperature is preferred. From the above perspective, a temperature below 0°C is preferred, more preferably below -5°C, more preferably below -10°C, and more preferably below -15°C. On the other hand, if the temperature is too low, the thermosetting sheet becomes uncured and its glass transition temperature (Tg) is below the temperature at which it is easily broken. Therefore, a temperature of -50°C or higher is preferred, and in the case of an epoxy compound, a temperature of -30°C or higher is more preferably preferred, and a temperature of -25°C or higher is even more preferably preferred.

[0376] Regarding the duration of low-temperature curing, there is no particular limitation as long as the composition of the present invention is frozen. Rapid freezing for at least 10 minutes is sufficient, preferably at least 30 minutes, preferably at least 1 hour, more preferably at least 2 hours, more preferably at least 4 hours, more preferably at least 8 hours, more preferably at least 16 hours, and more preferably at least 24 hours. On the other hand, since epoxy compounds react slowly even at low temperatures, from the viewpoint of avoiding long-term storage, it is preferable to store for 365 days or less, preferably 180 days or less, preferably 90 days or less, preferably 30 days or less, and preferably 7 days or less.

[0377] Furthermore, no pressure is required during low-temperature curing, but a small pressure of less than 0.1 kPa can be applied.

[0378] (Pressure process)

[0379] Next, considering the purpose of bonding the inorganic fillers together to form a heat-conducting path, eliminating the pores and voids in the cured product of the thermosetting sheet, i.e., the heat-conducting sheet, and improving the adhesion between the cured product of the thermosetting sheet, i.e., the heat-conducting sheet, and the substrate, it is desirable to pressurize the resulting sheet-like composition of the present invention.

[0380] However, depending on the purpose, pressure may not be applied.

[0381] For example, in cases with high solvent or inorganic filler content, a significant amount of solvent may remain in the pores after solvent removal. Therefore, in such cases, a pressurization process is preferred. By implementing a pressurization process, the voids (pores), especially the interconnecting pores, within the cured material of this thermosetting sheet, i.e., the thermally conductive sheet, can be reduced or minimized.

[0382] Ideally, the pressurization process should be carried out by applying a load of 2 MPa or more to the sheet-like composition of the present invention on the substrate.

[0383] Examples of pressurization methods include: flat plate pressing, hydrostatic pressing, vacuum pressing, calendering, belt pressing, and servo pressing. However, it is not limited to these methods.

[0384] The load is preferably 5 MPa or more, more preferably 7 MPa or more, and even more preferably 9 MPa or more. Furthermore, the load is preferably 1500 MPa or less, more preferably 1000 MPa or less, and even more preferably 800 MPa or less.

[0385] By setting the load under pressure below the aforementioned upper limit, voids in the sheet-like composition of the present invention can be eliminated without damaging the secondary particles of the inorganic filler, such as boron nitride aggregates, thereby improving the thermal conductivity of the cured thermosetting sheet, i.e., the thermally conductive sheet. By setting the load above the aforementioned lower limit, the contact between the inorganic fillers becomes better, making it easier to form a heat conduction path; therefore, the thermal conductivity of the cured thermosetting sheet, i.e., the thermally conductive sheet, can be improved.

[0386] The heating temperature of the sheet-like composition of the present invention on the substrate during the pressing process is not particularly limited. The heating temperature (product temperature) is preferably 0°C or higher, more preferably 5°C or higher, and even more preferably 10°C or higher. The heating temperature is preferably 300°C or lower, more preferably 250°C or lower, even more preferably 200°C or lower, even more preferably 100°C or lower, and particularly preferably 90°C or lower.

[0387] By performing a pressurization process within this temperature range, the melt viscosity of the resin in the sheet-like composition of the present invention can be reduced, further reducing the porosity and voids within the cured product of the thermosetting sheet, i.e., the thermally conductive sheet. Furthermore, by heating below the aforementioned upper limit, there is a tendency to suppress porosity caused by the decomposition of organic components and residual solvents in the thermosetting sheet and its cured product, i.e., the thermally conductive sheet.

[0388] There is no particular limitation on the time of the pressurization process. The pressurization process is preferably 30 seconds or more, more preferably 1 minute or more, further preferably 3 minutes or more, and particularly preferably 5 minutes or more. The pressurization process is preferably 1 hour or less, more preferably 30 minutes or less, and further preferably 20 minutes or less.

[0389] By setting the pressurization time below the aforementioned upper limit, there is a tendency to reduce the manufacturing time of this thermosetting sheet and decrease production costs. By setting the pressurization time above the aforementioned lower limit, there is a tendency to sufficiently remove the solidified material of this thermosetting sheet, i.e., the voids and pores within this thermally conductive sheet, thereby improving heat transfer performance and voltage resistance characteristics.

[0390] <This cured product and this sheet-like cured product>

[0391] This cured product and this sheet-like cured product can make the following physical properties, namely, the fracture energy obtained by three-point bending at 190°C, the fracture energy obtained by three-point bending at 150°C, the ratio of the fracture energy x obtained by three-point bending at 190°C to the fracture energy y obtained by three-point bending at 150°C (x / y), the Young's modulus obtained by three-point bending at 190°C, the Young's modulus obtained by three-point bending at 150°C, the thermal conductivity in the thickness direction at 25°C, the insulation breakdown voltage at a thickness of 150 μm, the volume resistivity (1000V, 200°C), the moisture absorption, the storage modulus at 200°C, and the glass transition temperature (Tg) within the ranges described above.

[0392] <This thermal conductive sheet>

[0393] In one embodiment of the present invention, the thermally conductive sheet is simply a thermally conductive sheet formed from the cured material. In other words, any thermally conductive sheet composed of the cured sheet is acceptable.

[0394] For this thermally conductive sheet, the physical properties, namely the fracture energy obtained by three-point bending at 190°C, the fracture energy obtained by three-point bending at 150°C, the ratio of the fracture energy x obtained by three-point bending at 190°C to the fracture energy y obtained by three-point bending at 150°C (x / y), the Young's modulus obtained by three-point bending at 190°C, the Young's modulus obtained by three-point bending at 150°C, the thermal conductivity in the thickness direction at 25°C, the insulation breakdown voltage, the volume resistivity (1000V, 200°C), the moisture absorption rate, the storage modulus at 200°C, and the glass transition temperature (Tg), can also be within the ranges described above.

[0395] (thickness)

[0396] The lower limit of the thickness of this thermally conductive sheet is preferably 50 μm or more, more preferably 60 μm or more, and even more preferably 70 μm or more. On the other hand, the upper limit of the thickness is preferably 400 μm or less, more preferably 300 μm or less, and even more preferably 250 μm or less.

[0397] By setting the thickness of this thermally conductive sheet to 50 μm or more, sufficient voltage withstand characteristics can be ensured. On the other hand, by setting it to 400 μm or less, especially when the thermally conductive sheet is used in power semiconductor devices, miniaturization and thinning can be achieved. In addition, compared with insulating thermally conductive layers formed of ceramic materials, the effect of reducing thermal resistance in the thickness direction based on thin film formation can be obtained.

[0398] <Manufacturing Method of This Thermally Conductive Sheet>

[0399] Next, an example of the manufacturing method of this thermally conductive sheet will be described.

[0400] This thermally conductive sheet can be cured by curing the thermosetting sheet made as described above to produce this thermally conductive sheet as a sheet-like cured product (this process is also referred to as the "curing process").

[0401] (Curing process)

[0402] The thermosetting sheet prepared as described above can be cured by heating.

[0403] At this point, the heating temperature (product temperature) is preferably 30–400°C, preferably above 50°C, preferably above 90°C, preferably above 120°C, preferably above 150°C, and preferably above 175°C. On the other hand, it is preferably below 300°C, and more preferably below 250°C.

[0404] The curing process, which allows the thermosetting sheet to fully cure, can be performed under pressure or without pressure. Alternatively, the pressure process and the curing process can be performed simultaneously.

[0405] Especially in the sheeting process after the pressurization and curing processes, it is preferable to apply the load within the above range for pressurization and curing.

[0406] There is no particular limitation on the load during simultaneous pressurization and curing. In this case, for example, it is preferable to apply a load of 5 MPa or more to the thermosetting sheet on the substrate, more preferably 7 MPa or more, and even more preferably 9 MPa or more. Furthermore, the load is preferably 2000 MPa or less, more preferably 1500 MPa or less, more preferably 1000 MPa or less, even more preferably 500 MPa or less, and even more preferably 100 MPa or less.

[0407] By setting the load during simultaneous pressurization and curing below the aforementioned upper limit, voids can be eliminated in this thermosetting sheet without damaging the secondary particles of inorganic fillers, such as boron nitride aggregates, thereby improving the thermal conductivity of the sheet. Furthermore, by setting the load above the aforementioned lower limit, the contact between the inorganic fillers becomes better, facilitating the formation of thermal conduction paths, thus further improving the thermal conductivity of the sheet.

[0408] There is no particular limitation on the pressurization time when pressurization and curing are performed simultaneously. The pressurization time is preferably 30 seconds or more, more preferably 1 minute or more, further preferably 3 minutes or more, and particularly preferably 5 minutes or more. In addition, the pressurization time is preferably 4 hours or less, more preferably 3 hours or less, and further preferably 2 hours or less.

[0409] By applying pressure for a time below the upper limit mentioned above, the manufacturing time of this thermally conductive sheet can be shortened, and production costs can be reduced. By applying pressure for a time above the lower limit mentioned above, voids and pores within this thermally conductive sheet can be sufficiently removed, thereby improving heat transfer performance and voltage resistance characteristics.

[0410] <This composite molded body>

[0411] As an example of an embodiment of the present invention, the composite molded body (also referred to as "this composite molded body") has a cured part formed from the sheet-like cured material of the composition of the present invention, namely the thermally conductive sheet, and a metal part, wherein the cured part and the metal part are integrally laminated.

[0412] At this time, the metal part may be provided on only one side of the cured part formed by the thermally conductive sheet, or it may be provided on two or more sides. For example, the metal part may be provided on only one side of the thermally conductive sheet, or it may be provided on both sides. In addition, the metal part may also be patterned.

[0413] Such a composite molded body can be manufactured by using a metal part as the aforementioned substrate, and forming the thermally conductive sheet on the substrate according to the above method. Alternatively, it can be manufactured by peeling the thermally conductive sheet, which is formed on a substrate different from the metal part, from the substrate and then heating and pressing it onto a metal component that becomes the metal part.

[0414] In this case, except for coating on a substrate such as PET that can be treated with a release agent, the thermally conductive sheet is made in the same manner as described above. Then, it is peeled off from the substrate and placed on another metal plate, or it is pressed between two metal plates to achieve integration.

[0415] As the metal plate, a metal plate with a thickness of about 10 μm to 10 cm made of copper, aluminum, nickel-plated metal, etc. can be used. In addition, the surface of the metal plate can be physically roughened or chemically treated with a surface treatment agent, etc. From the viewpoint of the adhesion between this thermally conductive sheet and conductive materials such as metal plates and circuit boards, these treatments are more preferred.

[0416] Specific examples of this composite molding include heat-dissipating laminates, heat-dissipating circuit boards, and power semiconductor devices. These will be described in turn below. However, it is not limited to these.

[0417] <This heat dissipation laminate>

[0418] The heat dissipation laminate (also referred to as "this heat dissipation laminate") of one embodiment of the present invention is any laminate that includes the thermally conductive sheet.

[0419] As an example of this heat dissipation laminate, a heat dissipation laminate in which a heat dissipation metal layer containing a heat dissipation material is laminated on one surface of the thermally conductive sheet can be cited.

[0420] There are no particular limitations on the heat dissipation material as long as it is made of a material with good thermal conductivity. However, in order to improve the thermal conductivity in the laminated structure, a heat dissipation metal material is preferred, and a flat metal material is even more preferred.

[0421] There are no particular restrictions on the type of metal material. However, considering good thermal conductivity and relatively low price, copper plates, aluminum plates, and aluminum alloy plates are preferred.

[0422] Regarding the integrated lamination of the thermally conductive sheet and the heat-dissipating metal layer, a batch molding process is preferred. In this case, the molding equipment, molding conditions, etc., can be within the same range as the molding conditions used to obtain the thermally conductive sheet. However, they do not necessarily need to be within the same range.

[0423] <This heat dissipation circuit board>

[0424] The heat-dissipating circuit board (also referred to as "this heat-dissipating circuit board") of one embodiment of the present invention only needs to have this thermally conductive sheet.

[0425] As an example of this heat-dissipating circuit board, a heat-dissipating circuit board with the following configuration can be cited: the aforementioned heat-dissipating metal layer is stacked on one surface of the thermally conductive sheet, and a conductive circuit is formed on the surface of the thermally conductive sheet on a side different from the heat-dissipating metal layer, and the circuit board is formed, for example, by etching. Specifically, a heat-dissipating circuit board that is integrally formed by "heat-dissipating metal layer / thermally conductive sheet / conductive circuit" can be cited. As a state before circuit etching, for example, an integral configuration of "heat-dissipating metal layer / thermally conductive sheet / conductive circuit forming metal layer" can be cited, in which the conductive circuit forming metal layer is flat and formed on the entire surface of one side of the thermally conductive sheet; or in which it is formed on a portion of the area of ​​one side of the thermally conductive sheet.

[0426] There are no particular limitations on the material of the metal layer used to form the conductive circuit. However, from the perspectives of conductivity, etchability, and cost, it is generally preferred to form it from a copper sheet with a thickness of 0.05 mm or more and 1.2 mm or less.

[0427] <This power semiconductor device>

[0428] An example of the power semiconductor device of the present invention (also referred to as "this power semiconductor device") is a product that integrates a circuit composed of multiple power semiconductors into a single packaged module, as long as it has this thermally conductive sheet.

[0429] As an example of this power semiconductor device, an apparatus in which a power semiconductor is mounted on a heat dissipation circuit board using this thermally conductive sheet can be cited.

[0430] In this power semiconductor device, components other than the thermally conductive sheet or the heat dissipation stack, such as aluminum wiring, sealing materials, packaging materials, heat sinks, thermal paste, and solder, may appropriately adopt conventionally known components.

[0431] <<Explanation of the statement>>

[0432] In this invention, when referred to as "α to β" (α and β are arbitrary numbers), unless otherwise specified, it includes the meaning of "above α and below β", and also includes the meaning of "preferably greater than α" or "preferably less than β".

[0433] Furthermore, when it is recorded as "α or above" or "α ≤" (α is any number), unless otherwise specified, it includes the meaning of "preferably greater than α". When it is recorded as "β or below" or "≤ β" (β is any number), unless otherwise specified, it includes the meaning of "preferably less than β".

[0434] In this invention, the term "sheet" conceptually includes sheets, films, and strips.

[0435] In addition, in this specification, the word "or" means "and / or".

[0436] Example

[0437] Hereinafter, an example of an embodiment of the present invention will be described. However, the present invention is not limited to the embodiment described below.

[0438] <Raw materials>

[0439] The raw materials used in the examples and comparative examples are described below.

[0440] (Inorganic packing)

[0441] • Inorganic filler 1: Spherical boron nitride aggregates with a carousel structure manufactured according to the method for manufacturing boron nitride aggregates disclosed in the examples of International Publication No. 2015 / 561028.

[0442] Maximum particle size (Dmax): 90 μm

[0443] Average particle size (D50): 45 μm

[0444] • Inorganic filler 2: Manufactured by Admatechs

[0445] Spherical alumina particles

[0446] Average particle size (D50): 7–13 μm

[0447] The maximum particle size (Dmax) and average particle size (D50) of the inorganic filler are determined by dispersing the inorganic filler in a pure water medium containing sodium hexametaphosphate as a dispersing stabilizer, measuring the volume-based particle size distribution using a laser diffraction / scattering particle size distribution measuring device LA-300 (manufactured by Horiba Corporation), and calculating the maximum particle size (Dmax) and the cumulative 50% volume particle size (average particle size (D50)) based on the obtained particle size distribution.

[0448] (Epoxy compounds)

[0449] • Epoxy Compound 1: Manufactured by Mitsubishi Chemical Corporation, a biphenyl-type solid epoxy compound with two glycidyl groups per molecule.

[0450] Mass-average molecular weight (Mw): Approximately 400

[0451] Epoxy equivalent (WPE): 200g / equivalent

[0452] • Epoxy Compound 2: Manufactured by Nagase ChemteX Inc., a multifunctional epoxy compound containing a structure with four or more glycidyl groups within one molecule.

[0453] It does not contain amine or amide structures containing nitrogen atoms.

[0454] Mass-average molecular weight (Mw): Approximately 400

[0455] Epoxy equivalent (WPE): 100g / equivalent

[0456] • Epoxy Compound 3: Alkyl diglycidyl ether manufactured by Mitsubishi Chemical Corporation, a multifunctional epoxy compound having two glycidyl groups per molecule.

[0457] Mass-average molecular weight (Mw): Approximately 240

[0458] Epoxy equivalent (WPE): 120g / equivalent

[0459] • Epoxy Compound 4: Manufactured by Mitsubishi Chemical Corporation, a bisphenol A type phenolic varnish-type solid epoxy compound, containing a multifunctional epoxy compound with a structure of four or more glycidyl groups within one molecule.

[0460] It does not contain amine or amide structures containing nitrogen atoms.

[0461] Mass-average molecular weight (Mw): ≥1,000 and <5,000

[0462] Epoxy equivalent (WPE): 210g / equivalent

[0463] • Epoxy Compound 5: Manufactured by Mitsubishi Chemical Corporation, bisphenol A type diglycidyl ether, a multifunctional epoxy compound with two glycidyl groups per molecule.

[0464] Mass-average molecular weight (Mw): Approximately 400

[0465] Epoxy equivalent (WPE): 200g / equivalent

[0466] (Curing agent)

[0467] • Hardener 1: "H-4" manufactured by UBE Corporation, a phenolic resin-based hardener (phenolic varnish).

[0468] • Curing agent 2: Manufactured by Shikoku Chemical Co., Ltd., Pd type benzoxazine, solid (25°C), X in formula (III) 2 CH2

[0469] • Hardener 3: "MEH-8000H" manufactured by Meiwa Kasei Corporation, a phenolic resin-based hardener (allyl phenol varnish).

[0470] (polymer)

[0471] • Epoxy polymer 1: A difunctional epoxy polymer manufactured by Mitsubishi Chemical Co., Ltd., disclosed as resin component 1 in Japanese Patent Application Publication No. 2020-63438, having the above-described structures (2) and (3), wherein R in formula (2) 3 For structure (4), R in equation (3) 4 R 5 R 6 R 7 All are methyl groups.

[0472] Polystyrene converted mass-average molecular weight (Mw): 30,000

[0473] Epoxy equivalent (WPE): 9,000 g / equivalent

[0474] (Thermosetting catalyst)

[0475] • Thermosetting catalyst 1: 2,4-Diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-triazine, having both an imidazolium-derived structure and a triazine-derived structure in one molecule (manufactured by Shikoku Chemical Co., Ltd., "Curezol 2E4MZ-A"), melting point: 215-225℃

[0476] • Thermosetting catalyst 2: 2-Phenyl-4,5-dihydroxymethylimidazol (manufactured by Shikoku Chemical Co., Ltd., "Curezol 2PHZ-PW"), melting point: dec. 230, therefore the melting point is above 230°C.

[0477] (Silane coupling agent)

[0478] • Silane coupling agent 1: Glycidyloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd. KBM-403)

[0479] <Examples 1-4, Comparative Examples 1-5>

[0480] Each raw material was weighed in accordance with the composition (parts by mass) shown in Table 1, and mixed using a rotary stirring device to prepare a mixture. In preparing this mixture, a slurry-like thermosetting composition was prepared by using 20% ​​by mass each of methyl ethyl ketone and cyclohexanone, such that the above mixture constitutes 60% by mass (solid component concentration) in the coating slurry.

[0481] The obtained slurry-like thermosetting composition was coated onto a PET substrate using a doctor blade method and dried at 60°C (heating atmosphere temperature) for 120 minutes to obtain a sheet-like thermosetting composition. The total content of methyl ethyl ketone and cyclohexanone in the sheet-like thermosetting composition was less than 1% by mass.

[0482] Next, regarding Examples 1-4 and Comparative Examples 1-4, the sheet-like thermosetting composition was placed in a vacuum-sealed bag, the air inside the bag was removed, and the opening of the bag was heat-sealed. Then, the bag was stored in a freezer at -20°C for 72 hours to perform low-temperature curing. Regarding Comparative Example 5, the low-temperature curing was not performed; instead, the vacuum-sealed bag containing the sheet-like thermosetting composition was cured at 60°C for 72 hours.

[0483] Next, the sheet-like thermosetting compositions obtained in Examples 1-4 and Comparative Examples 1-5 were placed in a pressure press and pressurized at 40°C with a load of 150 MPa for 10 minutes to produce sheet-like thermosetting compositions (samples).

[0484] <Measurement and Evaluation>

[0485] For the raw materials used in each embodiment and comparative example, WPE was measured as follows, and for the cured products (sheet cured products) of the sheet thermosetting composition (sample), three-point bending test, thermal conductivity, insulation breakdown voltage, volume resistivity, moisture absorption, storage modulus, and glass transition temperature (Tg) were measured as follows. Then, reflow solderability evaluation test and sintering resistance evaluation test were performed. The results of each embodiment and comparative example are shown in Table 1.

[0486] Furthermore, in Table 1, the values ​​for the amount of each component in the thermosetting composition (sample) are expressed as the mass ratio (parts by mass) of each component, and "WPE" is the epoxy equivalent (g / equivalent) of the resin component after removing the solvent and inorganic filler from the thermosetting composition.

[0487] (Determination of epoxy equivalent (WPE) of resin components)

[0488] For the thermosetting compositions obtained by mixing the resin components (the components after removing solvents and inorganic fillers from the thermosetting composition) used in each embodiment and comparative example, namely epoxy compounds 1, 2, 3, 4, 5, curing agents 1, 2, 3, epoxy polymer 1, thermosetting catalysts 1, 2, and silane coupling agent 1 in the mass ratios shown in Table 1 below, the potential was determined by potentiometric titration according to JIS K7236, converted to the value of the entire resin component, and the epoxy equivalent (g / equivalent) was calculated.

[0489] (Three-point bending test of cured thermosetting compositions)

[0490] The sheet-like thermosetting compositions (samples) prepared in each embodiment and comparative example were stacked in a state of 4 sheets, and were heated at 120°C (product temperature) for 30 minutes, 175°C (product temperature) for 30 minutes, and then heated at 200°C (product temperature) for 30 minutes to cure them, so as to obtain a sheet-like cured material with a thickness of 0.6 mm. The material was then cut into 50 mm × 8 mm pieces to make test pieces.

[0491] The obtained test pieces were measured using an Autograph AG-20kNXplus (manufactured by Shimadzu Corporation) under the following conditions.

[0492] Test piece shape: approximately 50mm × 8mm × 0.6mm

[0493] Test temperatures: 150℃, 190℃

[0494] Number of trials: n=2

[0495] Distance between pivots: 40mm

[0496] Support platform radius: 2mm

[0497] Indenter radius: 3.2mm

[0498] Test speed: 0.01 mm / s

[0499] The load is applied from the upper surface of the test piece to the center between the fulcrums, and ends at the point where the test piece fails (the fracture point).

[0500] Here, the strain ε is obtained by the following formula.

[0501] ε = (6 × ω × h) / (L × L)

[0502] In the formula, ω represents the displacement at the fracture point (mm), h represents the thickness of the test piece before the load is applied (mm), and L represents the distance between the support points (mm).

[0503] In addition, the fracture bending stress σ (kPa) is calculated by the following formula.

[0504] σ=(3×P×L) / (2×b×h×h)×1000

[0505] In the formula, P represents the load at the fracture point (N), b represents the width of the test sample before the load is applied (mm), h represents the thickness of the test piece before the load is applied (mm), and L represents the distance between the support points (mm).

[0506] Then, in the stress-strain curve with stress as the vertical axis and strain as the horizontal axis, the bending fracture energy per unit volume (kPa) is calculated by measuring the area under the curve up to the fracture point.

[0507] In the stress-strain curves described above, the slope of the strain from 0.01% to 0.1% is taken as Young's modulus and is calculated using the following formula.

[0508] Young's modulus (GPa)={σ(ε;0.1)-σ(ε;0.01)} / (0.1-0.01) / 1000000

[0509] Where σ(ε;0.1) is the stress at strain 0.1, and σ(ε;0.01) is the stress at strain 0.01.

[0510] (Determination of thermal conductivity in the thickness direction of sheet-like cured thermosetting compositions)

[0511] The sheet-like thermosetting compositions (samples) prepared in each example and comparative example were subjected to a load of 10 MPa and heated at 175°C (product temperature) for 30 minutes, followed by heating at 200°C (product temperature) for 30 minutes to cure them, thereby obtaining sheet-like cured products (samples) with a thickness of 150 μm.

[0512] In addition, the sheet-like thermosetting compositions (samples) prepared in each embodiment and comparative example were overlapped by 2, 3, or 4 sheets, and then pressurized and heated in the same manner as described above, thereby obtaining 4 sheet-like cured products (samples) with different thicknesses.

[0513] For these four sheet-like cured materials (samples) of different thicknesses, the following measurements were performed to determine the thermal conductivity at 25°C in the sheet thickness direction in a steady-state method, based on the slope expressed by the thermal resistance value relative to the sheet thickness (according to ASTM D5470).

[0514] (1) Thickness: The thickness (μm) when pressed using Mentor Graphics T3Ster-DynTIM at a pressing pressure of 3400 kPa.

[0515] (2) Measurement area: The area (cm²) of the heat transfer portion when measured using the Mentor Graphics T3Ster-DynTIM. 2 )

[0516] (3) Thermal resistance: The thermal resistance (K / W) of a T3Ster-DynTIM manufactured by Mentor Graphics when pressed at a pressure of 3400 kPa.

[0517] (4) Thermal conductivity: The thermal resistance of four sheet-like solidified materials (samples) with different thicknesses was measured, and the thermal conductivity (W / m·K) was calculated according to the following formula.

[0518] Formula: Thermal conductivity (W / m·K) = 1 / ((slope (thermal resistance / thickness): K / (W·μm)) × (area: cm²) 2 ))×10 -2

[0519] (Determination of BDV (Insulation Breakdown Voltage) of Flake Cured Thermosetting Compositions)

[0520] The sheet-like thermosetting compositions (samples) prepared in each embodiment and comparative example were overlapped on a 2 mm thick copper plate. While applying pressure with a load of 10 MPa, they were heated at 175°C (product temperature) for 30 minutes, followed by heating at 200°C (product temperature) for 30 minutes. The mixture was cured by heating and pressure to bond the composite. A sheet-like cured material with a thickness of 150 μm was laminated on the copper plate to prepare a composite molded body (evaluation sample).

[0521] The composite molded body (evaluation sample) was immersed in insulating oil (3M "Fluorinert FC-40"), and an ultra-high voltage withstand voltage tester 7470 (made by the Institute of Measurement Technology) was used. Electrodes were placed on a patterned φ25mm copper plate, and a voltage of 0.5kV was applied, increasing by 500V every minute until the sheet-like solidified material was destroyed. The voltage at this point was measured (BDV: insulation breakdown voltage).

[0522] (Determination of volume resistivity of sheet-like cured thermosetting compositions)

[0523] The sheet-like thermosetting compositions (samples) prepared in each example and comparative example were cut into test pieces of 8.5cm × 8.5cm. While applying a load of 10MPa from above and below, they were heated at 120°C (product temperature) for 30 minutes, then at 175°C (product temperature) for 30 minutes, and then at 200°C (product temperature) for 30 minutes to cure them, thereby obtaining sheet-like cured products with a thickness of 150μm, which were used as evaluation samples.

[0524] For this evaluation sample, the volume resistivity was measured using the following measuring apparatus: a digital ultraresistivity / micro-ammeter 5451 (manufactured by ACDMT) and a resistivity test kit 12708 (manufactured by ESPEC) under the following conditions.

[0525] Main electrode outer diameter: 50mm

[0526] Inner diameter of protective electrode: 70mm

[0527] Measurement temperature conditions: 200℃

[0528] Measurement voltage: 1000V

[0529] Power frequency: 50Hz

[0530] Current limiter: 10mA

[0531] Discharge time: 10 seconds

[0532] Charging time: 1 minute

[0533] Measurement interval: 2 seconds

[0534] Number of measurements: 90 seconds

[0535] (Determination of moisture absorption rate of sheet-cured thermosetting compositions)

[0536] The sheet-like thermosetting compositions (samples) prepared in each example and comparative example were cut into 6cm×7cm pieces. While applying a load of 10MPa from above and below, they were heated at 120°C (product temperature) for 30 minutes, then at 175°C (product temperature) for 30 minutes, and then at 200°C (product temperature) for 30 minutes to cure them, thereby obtaining sheet-like cured products with a thickness of 150μm, which were used as evaluation samples.

[0537] The evaluation sample was dried at 150°C (product temperature) for 1 hour, and its mass a was measured. Then, these sheet-like resin-cured materials were stored in a constant temperature and humidity chamber (SH-221, manufactured by ESPEC) at 85°C and 85%RH for a certain period, and their mass was measured over time until a constant mass (constant weight) b was achieved. The mass gain rate was calculated using the following formula, and this mass gain rate was taken as the moisture absorption rate.

[0538] Moisture absorption rate (mass%) = mass increase rate (%) = ((ba) / a) × 100

[0539] (Determination of storage modulus (E') of sheet-cured thermosetting compositions)

[0540] Three sheets of the thermosetting composition (sample) prepared in each example and comparative example were stacked together. While applying a load of 10 MPa from above and below, the sheets were heated at 120°C (product temperature) for 30 minutes, at 175°C (product temperature) for 30 minutes, and then at 200°C (product temperature) for 30 minutes to cure them, thereby obtaining a sheet-like cured material with a thickness of 450 μm. The cured material was cut into pieces with a width of 4 mm and a length of about 50 to 60 mm, and the resulting test pieces were used as evaluation samples.

[0541] For this evaluation sample, the energy storage modulus (E') was measured using a Hitachi High Technology Corporation "DMS6100" under the following conditions. The energy storage modulus (E') at 200°C is shown in the table.

[0542] Measurement temperature conditions: -110~270℃, heating rate 10℃ / min

[0543] Measurement mode: Tensile mode

[0544] Measurement frequency: 1Hz

[0545] Chuck spacing: 35mm

[0546] Strain amplitude (μm): 5μm

[0547] Initial force amplitude (mN): 50mN

[0548] (Determination of the glass transition temperature (Tg) of sheet-cured thermosetting compositions)

[0549] The evaluation sample was prepared in the same manner as the above energy storage modulus determination. The energy storage modulus and loss modulus were measured under the same conditions as the above energy storage modulus determination, and Tg (°C) was obtained from the peak value of Tanδ.

[0550] (Evaluation of reflow soldering resistance)

[0551] Copper plates with thicknesses of 500 μm and 2,000 μm were prepared, each having undergone 100 roughening treatments on its surface using a #120 file. One of these copper plates was used to clamp the sheet-like thermosetting composition (sample) obtained in each example and comparative example. With the two copper plates clamping it from top to bottom, a pressure of 10 MPa was applied. Under this condition, the mixture was heated and pressurized at 120°C (product temperature) for 30 minutes, followed by heating and pressurizing at 175°C (product temperature) for 30 minutes, and then heating and pressurizing at 200°C (product temperature) for 30 minutes to cure it, obtaining a composite molded body for reflow soldering tests. The thickness of the cured sheet-like composite molded body was 150 μm.

[0552] The obtained composite molded body is patterned by etching a 500μm copper plate. The pattern is designed to retain two circular patterns with a diameter of 25mm.

[0553] Using a constant temperature and humidity chamber SH-221 (manufactured by ESPEC), the composite molded body prepared as described above for reflow soldering test was stored in an environment of 85°C and 85%RH for 3 days. Then, in a nitrogen atmosphere, the temperature was raised from room temperature to 290°C (product temperature) in 12 minutes over 30 minutes. After being held at 290°C (product temperature) for 10 minutes, it was cooled to room temperature (moisture absorption reflow soldering test).

[0554] If the BDV (insulation breakdown voltage) after the above reflow soldering test is less than 5kV, the reflow soldering resistance is evaluated as "×: unqualified"; if it is above 5kV, it is evaluated as "〇: qualified".

[0555] (Evaluation of sintering resistance)

[0556] Copper plates with thicknesses of 500 μm and 1,000 μm, with surfaces chemically roughened, were prepared. With one of these copper plates sandwiching each sheet of the thermosetting composition (sample) obtained in each example and comparative example, a pressure of 10 MPa was applied at 120°C (product temperature) for 30 minutes, followed by a pressure of 10 MPa at 175°C (product temperature) for 30 minutes, and then a pressure of 10 MPa at 200°C (product temperature) for 30 minutes, to heat-pressurize the material. This created a laminate with metal portions (copper plates) on the top and bottom of the cured sheet. The 500 μm thick copper plates in these metal portions were then etched to create a pattern, resulting in a composite molded body with a circuit pattern on the upper surface. At this point, the thickness of the cured sheet was 150 μm.

[0557] Next, evaluation samples simulating the silver sintering process were prepared.

[0558] The composite molded body is about 100 mm thick.2 A copper plate with a thickness of 0.2 mm × 5 mm × 4 mm is placed on the circuit pattern to form an analog chip, and then covered with a 0.1 mm thick Teflon sheet as a buffer material. ™ It is made of composite molded body, copper plate and Teflon. ™ The laminated body is clamped with an SUS plate and heated and pressurized for 10 minutes at 250°C (product temperature) with the pressure applied to the 0.2 mm copper plate set to 19 MPa to produce an evaluation sample.

[0559] For the evaluation sample obtained by the process of simulating silver sintering as described above after heating and pressurization, the interface between the 500 μm thick copper plate and the sheet-like solidified material was observed using the FineSAT (FS300III) ultrasonic imaging device (manufactured by Hitachi Power Solutions).

[0560] In addition, observation using an ultrasonic imaging device was performed by placing the evaluation sample in water with a probe at a frequency of 50 MHz, a gain of 30 dB, and a spacing of 0.1 mm.

[0561] When delamination occurs at the interface between the copper plate and the sheet-like cured material, the sintering resistance is evaluated as "×: unqualified"; when no delamination occurs, it is evaluated as "〇: qualified".

[0562] (Laser flash thermal conductivity)

[0563] Three sheets of the thermosetting composition (sample) prepared in Examples 1 and 2 were stacked together. While applying a load of 10 MPa from above and below, the sheets were heated at 120°C (product temperature) for 30 minutes, at 175°C (product temperature) for 30 minutes, and then at 200°C (product temperature) for 30 minutes to cure the product. This yielded a sheet-like cured material with a thickness of approximately 450 μm. The cured material was cut into specified sizes, and the resulting test pieces were used as evaluation samples.

[0564] The thermal diffusivity, density, and specific heat are measured as described below, and the thermal conductivity is calculated using these values.

[0565] =Determination of thermal diffusivity=

[0566] The diffusion rate (m) was determined under the following conditions. 2 / s).

[0567] Measurement Apparatus: Xe Flash Analyzer LFA447

[0568] Measurement temperature: Measurement was performed at temperatures ranging from 25℃ to 175℃ (results at 150℃ and 175℃).

[0569] Evaluation sample: sheet-like, 1cm x 1cm, approximately 400–500μm thick.

[0570] =Determination of specific heat=

[0571] Specific heat (J / KgK) was determined under the following conditions.

[0572] Analytical method: Differential scanning calorimetry

[0573] Device: Differential Scanning Calorimeter (DSC) Hitachi High-Tech Corporation DSC600 (Electric Cooler)

[0574] Sample size: Approximately 10 mg

[0575] Temperature control program: Maintain 0℃ (5 minutes) ~ Maintain 50℃ (5 minutes) ~ Maintain 150℃ (5 minutes) ~ Maintain 200℃ (5 minutes) Heating rate: 10℃ / min

[0576] Atmosphere: N 230ml / min

[0577] Sample container: Al sample container

[0578] Test groups: empty container, standard sample + container, sample + container

[0579] Standard sample: Synthetic sapphire (9.925 mg) [0.775 J / g * ℃ (25℃)]

[0580] Measurement: The specific heat of the cured material at 150℃ and 175℃ was measured.

[0581] =Determination of linear expansion rate=

[0582] The linear expansion rate was determined by thermomechanical analysis (TMA) under the following conditions.

[0583] Measurement apparatus: TMA7100 thermomechanical analyzer (manufactured by Hitachi High Technology Co., Ltd.)

[0584] Measurement mode: Tensile mode

[0585] Sample: Sheet-shaped, 30mm × 3mm × 400~500μm

[0586] Chuck spacing: 20mm

[0587] Atmosphere: Nitrogen gas flow rate of 200 mL / min; Heating rate: 5℃ / min

[0588] Temperature measurement steps: Step 1: -50~230℃; Step 2: 230~-50℃; Step 3: -50~230℃

[0589] The linear expansion rate was measured in the third step at 21℃~150℃ and 21℃~175℃.

[0590] =Density Measurement=

[0591] Density was determined under the following conditions.

[0592] Device Name: Archimedes Densitometer manufactured by Mettler Toledo

[0593] Water temperature: 21℃

[0594] Set the volume expansion rate to 3 times the linear expansion rate measured by TMA, and calculate the density at 150℃ and 175℃.

[0595] =Calculation and Evaluation of Thermal Conductivity=

[0596] Using the thermal diffusivity, density, and specific heat measured as described above, the thermal conductivity at 150°C and 175°C is calculated using the following formula.

[0597] Thermal conductivity (W / mK) = Thermal diffusivity (m 2 / s) × density (kg / m 3 ) × specific heat (J / KgK)

[0598] The ratio of thermal conductivity λ(175℃) at 175℃ to thermal conductivity λ(150℃) at 150℃ is as follows: λ(175℃) / λ(150℃) is less than 0.92 and is rated as "× (very unsatisfactory)", 0.92 or more but less than 0.95 and is rated as "△ (unsatisfactory)", 0.85 or more but less than 0.97 and is rated as "〇 (satisfactory)", and 0.97 or more and is rated as "◎ (very satisfied)".

[0599] (Bending resistance of sheet thermosetting compositions (mandrel test))

[0600] For Examples 1-4, each raw material was weighed to form the composition (parts by mass) shown in Table 1, and mixed using a rotary stirring device to prepare a mixture. In preparing this mixture, a slurry-like thermosetting composition was prepared by using 20% ​​by mass each of methyl ethyl ketone and cyclohexanone, respectively, such that the mixture constituted 60% by mass (solid component concentration) in the coating slurry.

[0601] The obtained slurry-like thermosetting composition was coated onto a PET substrate using a doctor blade method and dried at 60°C (heating atmosphere temperature) for 120 minutes to obtain a sheet-like thermosetting composition. The total content of methyl ethyl ketone and cyclohexanone in the sheet-like thermosetting composition was less than 1% by mass.

[0602] Next, the sheet-like thermosetting composition was placed in a vacuum packaging bag, the air inside the bag was removed, and the opening of the bag was heat-sealed. Then, the bag was stored in a freezer at -20°C for 72 hours to perform low-temperature curing, resulting in the sheet-like thermosetting composition (sample).

[0603] Cut the prepared sheet-like thermosetting composition (sample) into pieces with a width of 2cm and a length of 15cm or more, and evaluate its bending resistance according to the test method of JISK5600-5-1.

[0604] 〇 (Qualified): The diameter of the clamp that caused the fragment to break is less than 10mm.

[0605] × (Unacceptable): The diameter of the clamp that caused the breakage is 10mm or more.

[0606] Furthermore, the sheet-like thermosetting composition was placed in a pressure press and pressurized by applying a load of 150 MPa at 40°C for 10 minutes, resulting in a film thickness of 140–160 μm.

[0607] [Table 1]

[0608]

[0609] As can be seen from the above embodiments and the test results previously conducted by the inventors, if the fracture energy of the cured thermosetting composition containing inorganic fillers and thermosetting compounds is 55 kPa or more as measured by three-point bending at 190°C and 80 kPa or more as measured by three-point bending at 150°C, then the insulation withstand voltage can be maintained even after the reflow soldering process. Furthermore, when bonded to a substrate under conditions where external force is further applied at high temperatures, such as sintering, high-temperature resistance can be obtained without cracking or delamination of the cured composition.

[0610] Furthermore, it is known that for cured thermosetting compositions containing inorganic fillers and thermosetting compounds, if the ratio (x / y) of the fracture energy x at 190°C to the fracture energy y at 150°C, obtained by three-point bending measurement, is 0.7 or more and 1.15 or less, and the value of x is 55 kPa or more, then even after being subjected to internal stress at high temperature, such as in a reflow soldering process, the insulation withstand voltage can be maintained. Furthermore, when bonded to a substrate under conditions where external force is further applied at high temperature, such as in sintering bonding, high-temperature resistance can be obtained without cracking or delamination of the cured material.

[0611] Thermosetting compositions tend to accumulate strain during curing, and stress induced by strain tends to accumulate at temperatures before and after the curing temperature. For example, in the case of thermosetting compositions containing epoxy compounds, stress induced by strain at 120–200°C tends to accumulate. Therefore, it is believed that by measuring the fracture energy at 150°C and 190°C in a three-point bending test and ensuring that these values ​​are specific, resistance to reflow soldering under internal stress at temperatures above 200°C and sintering under external force can be obtained. This not only provides insulation resistance but also reduces the likelihood of cracking in the sheet or peeling at the interface with the substrate.

[0612] In addition, it is believed that by maintaining the fracture energy at 190°C at a certain value and having a small difference between the fracture energy at 150°C and 190°C, the stress will be dispersed even when internal stress or external force is applied under conditions above 200°C, or when the temperature is subsequently reduced. In the reflow soldering process and sintering bonding, it not only has insulation resistance, but is also less prone to cracking in the sheet or peeling at the interface with the substrate.

[0613] In contrast, it is believed that: Regarding the comparative examples, Comparative Examples 1 and 2 have a large amount of polymers with a mass-average molecular weight (Mw) of 5,000 or more in 100% mass of the solid component after removing the inorganic filler, thus their fracture energy and x / y value are smaller. Comparative Example 3 has a large amount of polymers with a mass-average molecular weight (Mw) of 5,000 or more in 100% mass of the solid component after removing the inorganic filler, but does not contain polyfunctional epoxy compounds with 3 or more epoxy groups per molecule, thus its fracture energy at 150°C and 190°C is smaller. Although Comparative Example 4 contains polyfunctional epoxy compounds with 3 or more epoxy groups per molecule, it does not contain polymers with a mass-average molecular weight (Mw) of 5,000 or more, resulting in a high storage modulus at 200°C but insufficient toughness, thus its fracture energy at 150°C is smaller and its x / y value is larger. Comparative Example 5 did not undergo low-temperature curing, thus its water was not dispersed by freezing, resulting in porosity, thus its fracture energy and x / y value at 150°C and 190°C are smaller. As a result, it was found that the fracture energy values ​​obtained by the three-point bending test at 190°C and / or the fracture energy values ​​obtained by the three-point bending test at 150°C did not meet the specified range, or the ratio (x / y) of the fracture energy x obtained by the three-point bending test at 190°C to the fracture energy y obtained by the three-point bending test at 150°C and / or the value of x did not meet the specified range. When the substrate is subjected to internal stress at high temperature, such as in a reflow soldering process, it is possible to fail to maintain the insulation withstand voltage. Or when the substrate is bonded under conditions of further external force at high temperature, such as in sintering bonding, cracks may occur in the cured product or the bond may peel off.

[0614] On the other hand, the main reason for achieving the effect described in the examples can be attributed to adjusting the amount of polymer, such as epoxy polymer, in order to adjust the WPE of the resin component to a specified range by adjusting the curing agent acting on the epoxy compound, or by adjusting the amount of multifunctional epoxy compound to adjust the number of functional groups and molecular weight of the resin component, or by selecting a skeleton structure, or by adjusting the low-temperature curing conditions, etc., thereby increasing the crosslinking density and cohesion when the cured product is made, improving the elasticity and fracture energy at high temperatures, and enabling it to have insulation resistance at high temperatures and sintering resistance under high-temperature conditions.

[0615] Based on the above viewpoints, in order to obtain the thermosetting composition of the present invention, it is considered more preferable to prepare the composition of the present invention as follows: increase the content of the multifunctional epoxy compound as a thermosetting compound, and decrease the content of the polymer, such as the epoxy polymer, thereby using a phenolic resin-based curing agent as a curing agent to increase the crosslinking density of the cured product, and perform low-temperature curing.

[0616] In the embodiments that satisfy the aforementioned high-temperature resistance, the workability of the sheet thermosetting composition of Example 1 is further preferred, as evidenced by the evaluation results of the mandrel test. On the other hand, the decrease in thermal conductivity at high temperatures is further reduced in Example 2, as evidenced by the evaluation results of laser flash thermal conductivity. This is presumably because Example 1 contains a smaller amount of epoxy polymer than Example 2, thus maintaining the flexibility of the uncured sheet thermosetting composition. Furthermore, Example 2, containing phenolic resin and benzoxazine compound, suppresses the decrease in thermal conductivity at high temperatures compared to Example 1, resulting in less change in physical properties at high temperatures.

Claims

1. A thermosetting composition comprising an inorganic filler and a thermosetting compound, characterized in that, The cured product formed by curing the thermosetting composition (also known as "cured thermosetting composition") has a fracture energy of 55 kPa or more when measured by three-point bending at 190°C, and a fracture energy of 80 kPa or more when measured by three-point bending at 150°C.

2. A thermosetting composition comprising an inorganic filler and a thermosetting compound, characterized in that, When the fracture energy obtained by the curing of the thermosetting composition (also known as "cured thermosetting composition") through a three-point bending test at 190°C is set as x, and the fracture energy obtained by the three-point bending test at 150°C is set as y, the value of x / y is 0.7 or more and 1.15 or less, and the value of x is 55 kPa or more.

3. The thermosetting composition according to claim 1 or 2, characterized in that, The cured thermosetting composition has a Young's modulus of 5.5 GPa or higher, as determined by a three-point bending test at 190°C.

4. The thermosetting composition according to claim 1 or 2, characterized in that, The sheet-like cured product formed by curing the thermosetting composition (also known as "sheet-like cured product of thermosetting composition") has a thermal conductivity of 14 W / m·K or higher in the thickness direction at 25°C.

5. The thermosetting composition according to claim 1 or 2, characterized in that, The insulation breakdown voltage of the thermosetting composition when the thickness of the sheet-cured product is 150 μm is above 6.5 kV.

6. The thermosetting composition according to claim 1 or 2, characterized in that, The sheet-like cured product of the thermosetting composition has a volume resistivity of 3.0E+10Ωcm or higher at 1000V and 200℃.

7. The thermosetting composition according to claim 1 or 2, characterized in that, The moisture absorption rate of the sheet-cured thermosetting composition is 0.7% by mass or more and 1.2% by mass or less.

8. The thermosetting composition according to claim 1 or 2, characterized in that, The thermosetting composition has a storage modulus of 6.0 GPa or more and 100 GPa or less at 200°C.

9. The thermosetting composition according to claim 1 or 2, characterized in that, The glass transition temperature (Tg) of the sheet-cured product of the thermosetting composition is above 170°C.

10. The thermosetting composition according to claim 1 or 2, comprising an epoxy compound and at least one selected from phenolic resin, benzoxazine compound, polyarylate, cyanate ester and maleimide.

11. The thermosetting composition according to claim 1 or 2, comprising an epoxy compound and a phenolic resin.

12. The thermosetting composition according to claim 1 or 2, comprising a multifunctional epoxy compound having three or more epoxy groups within a molecule and a mass-average molecular weight (Mw) of less than 5,000.

13. The thermosetting composition according to claim 1 or 2, comprising a high molecular weight epoxy compound having a mass-average molecular weight (Mw) of 5,000 or more.

14. The thermosetting composition according to claim 1 or 2, wherein the composition contains a polymer with a mass-average molecular weight (Mw) of 5,000 or more in a proportion of 5% by mass and less than 30% by mass relative to 100% by mass of the solids after removing the inorganic filler.

15. The thermosetting composition according to claim 1 or 2, wherein the composition contains a polymer with a mass-average molecular weight (Mw) of 5,000 or more in a proportion of 5% by mass and 23% by mass or less of the solids after removing the inorganic filler, for a proportion of 100% by mass.

16. The thermosetting composition according to claim 1 or 2, comprising an epoxy compound, wherein the epoxy equivalent (WPE) of the solid component after removing the inorganic filler from the solid component of the thermosetting composition is 200 g / equivalent or more and less than 250 g / equivalent.

17. The thermosetting composition according to claim 1 or 2, wherein boron nitride aggregated particles are contained as the inorganic filler.

18. The thermosetting composition according to claim 1 or 2, wherein the inorganic filler is contained in a proportion of 30% by mass or more and less than 90% by mass relative to 100% by mass of the solids content of the entire composition.

19. A thermally conductive sheet formed from a sheet-like cured product of the thermosetting composition of claim 1 or 2.

20. A heat dissipation laminate comprising the thermally conductive sheet of claim 19.

21. A heat-dissipating circuit board comprising the thermally conductive sheet as described in claim 19.

22. A power semiconductor device comprising the thermally conductive sheet of claim 19.

23. A method for manufacturing a thermosetting sheet, characterized in that, The thermosetting composition according to claim 1 or 2 is formed into a film and then subjected to low-temperature curing at an ambient temperature below 0°C.

Citation Information

Patent Citations

  • Heat dissipation member, and manufacturing method of semiconductor module

    JP2013089670A

  • Boron nitride aggregated particle, composition containing boron nitride aggregated particle, and three-dimensional integrated circuit having layer comprising the composition

    JP2015006985A

  • Boron nitride aggregated particle, and method for producing the same, composition containing the same, and molding containing the same

    JP2016135730A

  • Heat release resin sheet and device containing heat release resin sheet

    JP2017036415A

  • Resin composition, resin cured product and composite molding

    JP2020063438A